Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 1315710115 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 1315710115 records from 25238 constituent datasets: 174 records from BIRDRACE Bon(n)apartem?wen. 10 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 538 records from Composici?n flor?stica y estructura de una parcela permanente en bosques h?medos tropicales del municipio de Pie de Pepe, Choc?. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 6642 records from Distribution of foraminifera of sediment core GIK23258-2. 2718 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 1189 records from UWIZM Molluscs. 32 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 4083 records from MCP-Aves - Cole??o de Aves. 2534 records from Elaboration de table de tarif de cubage multisp?cifique (I). 265 records from Nannofossil abundance of Hole 36-329. 521 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 ?m. 104 records from Nematode genera abundances at the Arctic H?kon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 38 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 371 records from orthopteracollections-nhmj-ioj. 778 records from Bird specimens of Saitama Museum of Natural History. 16 records from Insect Collections of Okomu National Park- Nigeria. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 412 records from Heinersdorfer Sumpfwiese. 133642 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 279489 records from ARABEL - Arachnologia Belgica. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 8 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 10788 records from Collections of Bioclass, school #179, Moscow. 53 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 988 records from flower availability 2008 Alb-korrigiert. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 13 records from Dinoflagellate abundance of Hole 14-144. 348 records from Antarctic pycnogonids. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 60949 records from MLZ Bird Collection (Arctos). 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 277417 records from Digitalizaci?n y sistematizaci?n de las colecciones biol?gicas del INECOL (Herbario). 34 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 269 records from Range table from benthic foraminifers in ODP Hole 161-974B. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 7 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 187 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 ?m). 1156 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 1714 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 18 records from Naturtag. 16071 records from Herbier Louis-Marie (QFA) - Collection de lichens. 93 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 11 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Sch?ffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (St?l, 1860) and revalidation of P. fuscescens (Dallas, 1851). 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 1551 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 127 records from Total foraminifera counts of multinet M21/2_MSN650. 7283 records from Colec??o Entomol?gica IIA. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 16763 records from MZFC/Coleccion de Aves. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 1057 records from DMNS Egg Collection (Arctos). 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 238 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 361 records from An updated checklist of aquatic plants of Myanmar and Thailand. 1702 records from BioGIS - Bryophytes - HUJ collections. 957 records from Collection de longicornes et autres col?opt?res saproxyliques de Lionel Valladares. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 2208 records from marine sediment metagenome Raw sequence reads. 13 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 776 records from Programme ACT : R?partition Pie bavarde 2010 - 2014 Coordonn?es GPS Lambert 93. 565 records from Colecci?n Zool?gica Universidad del Tolima (CZUT) - Ar?cnidos. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 423 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 9 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 66 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservaci?n Guanacaste in northwestern Costa Rica, with a key to their identification. 120 records from BIRDRACE The early birds. 462 records from Donn?es odonates collect?es par le CEN Aquitaine entre 1995 et 2015. 92 records from Protozoa Abundance_Microbial Parameters. 17 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 55 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 59788 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 32 records from Antarctic Pycnogonids II. 2560 records from Upper Silesian Museum, Bird Observations. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 847 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 243 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 127 records from SEWBReC Springtails and allies (South East Wales). 1 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 108 records from Benthic foraminifera abundance in ODP Leg 155 holes. 62 records from Polychaeta and Oligochaeta of the Auckland and Campbell Islands, New Zealand, 1941-1945. 158251 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgel?nde. 419 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 11 records from (Table 2) Population density and zoobenthos biomass in bottom communities of the Novosibirsk Polynya in September 2008. 286 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 69 records from BIRDRACE Pfeifenten. 5335 records from Marine metagenome ICM_JRV. 146 records from Donn?es de la naturaliste Laurence Beauchamp. 52 records from Collections ichtyologiques et herp?tologiques (BOUM). 288 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15046 records from Colecci?n de mariposas del Museo de Entomolog?a de la Universidad del Valle. 18 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 330 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 6192 records from NE Scotland fish records 1800-2010. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 57913 records from Fichier communal des ongul?s. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 25 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 9176 records from R?seau de surveillance Polynesia Mana - Peuplements de poissons. 115 records from Living Cirripedia. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 604 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125?m across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 218 records from Land and freshwater molluscs of Northern Spain. 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3775 records from Donn?es naturalistes de Charlotte PICARD. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 5 records from Ostracoda abundance of Hole 44-390. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 131 records from Manejo campesino sustentable del maguey papalote del Chilapan. Fase II. 28082 records from University of California Santa Barbara Invertebrate Zoology Collection. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 5460 records from Colecci?n de Fabales del Museo Bot?nico CORD - IMBIV. 85153 records from ALCB - Herb?rio Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 79214 records from Fish specimens of Kagoshima University Museum. 3814 records from UTEP Invertebrates (Arctos). 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolecci?n de la diversidad de razas de ma?z criollo en la regi?n de la Huasteca en M?xico para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 3569 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 108 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 878 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 884 records from Diversit? et distribution de quelques esp?ces de plantes agroforesti?res au B?nin. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), esp?ce calcicole end?mique de la Polyn?sie fran?aise, d?crite de l?atoll soulev? de Niau (Tuamotu). 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 15 records from Nannofossil abundance of Hole 10-93. 122 records from Base de datos de las especies maderables del g?nero Dalbergia en M?xico, registros del Herbario Nacional de M?xico (MEXU). 1422 records from Donn?es du/de la naturaliste Chevreau David provenant de la base de donn?e du SINP ?le-de-France CETTIA. 4 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 275 records from Planktic foraminifera counts of sediment core V14-77. 13 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 38 records from Ours 2006 pr?sence Occasionnelle Mailles 10km LAEA R?seau Ours brun ONCFS. 14 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 50 records from Herpetofauna de la expedici?n Pisba - Proyecto Boyac? BIO UPTC. 3876 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 251794 records from Phase 2 Lowland Grassland Survey of Wales. 60 records from Amphibian and Reptilian (KIEE-AR). 232 records from Filogenia de las cact?ceas columnares (Pachycereeae) con base en caracteres anat?mico-morfol?gicos. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79? N section). 5919 records from Cat?logo taxon?mico y biogeogr?fico de los radiolarios (orden Polycystina) de la regi?n central y sur del Golfo de California. 325 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 420 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 1044940 records from CLICNAT Base de donn?es naturaliste picarde g?r?e par Picardie Nature. 413272 records from DATAVES. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 17 records from Marine metagenome ICM_AGW. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 ?m. 78 records from Donn?es de la naturaliste Anna Even. 816 records from Esp?ces v?getales sur sable roux du fourr? de Ranobe, PK 32 Toliara. 882 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 61 records from pangolin and pangolin products seized by the customs and pangolin public aided record from 2010 to 2019. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 81 records from Kystfuruskoger i Tysnes og Fusa. 32 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 362 records from Centre d'Estudis Avan?ats de Blanes, Macroinvertebrados Limno. 29 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 509 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 91 records from Diatom abundance of Hole 95-613. 8 records from Die Bachspezies 2008/2009. 2364 records from Modelaci?n de la distribuci?n geogr?fica de las Orchidaceae del Soconusco. 73 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 1127 records from marine sediment metagenome Metagenome. 608 records from Range table from benthic foraminifers in ODP Hole 146-889A. 68 records from Streuobstwiese. 23 records from Abundance of benthos infauna at station GIK23042-2. 1968 records from Estudio flor?stico de los bosques mes?filos de la Sierra Mazateca de Oaxaca, M?xico. 371 records from Bannwald Burghauser Forst. 9 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 948 records from Bulletin du Mus?um d'Histoire Naturelle [1895- ]. 197 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 690 records from Benthic foraminifera counts of sediment core GIK23352-3. 290 records from Donn?es 2016 P?lobate brun Comit? D?partemental de Protection de la Nature et de l'Environnement. 82 records from R?ckkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 247 records from Flora vascular y no vascular: expedici?n Cuenca Media del r?o Chicamocha - Proyecto Boyac? BIO UPTC. 49 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 ?m fraction. 54 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 20 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 13 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 2779607 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 107 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 2127 records from ZUEC-OPH - Cole??o de Ophiuroidea do Museu de Zoologia da UNICAMP. 10 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 1009 records from Programme ACT : R?partition Merle noir 2012 - 2016 Coordonn?es GPS Lambert 93. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 173 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris ?ur?i?. 4617 records from Inventaire de la flore du Grand Poitiers 2009. 20520 records from University of Guam Insect Collection. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 832 records from Benthic foraminifera and algae abundance of Hole 81-552A. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1461 records from M. Gollop Collection. 1 records from Donn?es naturalistes d'Olivier DELZONS. 395 records from Planktic foraminifera abundance of Hole 32-310. 218 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 26 records from Dinoflagellate abundance of Hole 81-554. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 3 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 174 records from Artenvielfalt des "Gr?nen Klassenzimmers". 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 119 records from Nannofossil abundance of Hole 24-232. 177 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 7 records from Planktic foraminifera abundance of Hole 53-418B. 14 records from Berea College, Ralph L. Thompson Herbarium. 424 records from Distribution of nanoplankton at trap WR2. 642 records from An?lisis de la biodiversidad y servicios ecosist?micos para su aplicaci?n en la toma de decisiones en el departamento de Boyac?/Boyac? Bio-Flora El Consuelo. 84 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 1 records from New record of the genus Baetiella U?no, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 58 records from Donn?es du/de la naturaliste Williamson Thomas provenant de la base de donn?e du SINP ?le-de-France CETTIA. 20 records from Planktic foraminifera abundance of Hole 19-185. 50 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 18 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 6 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 4 records from A Catalogue and Historical Study of the Odonata of Ecuador. 1361 records from C?digos de barras de la vida en peces y zooplancton de M?xico. 10 records from Description of six new large species of Argentinomyia Lynch-Arribalzaga, 1891 and redescription of Talahua fervida (Fluke, 1945) (Diptera, Syrphidae, Syrphinae). 5 records from Loricifera - SMF. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 267 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 833 records from Plant species from the sacred and community forests of Mono departement. 479121 records from KTP Ring Data. 4 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 2252 records from Synth?se de la R?partition des populations de cerf ?laphe en 2000 (r?seau Ongul?s sauvages ONCFS-FNC-FDC). 483 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 41 records from Morphologische Daten von Natrix. 1478 records from Programme FLASH : R?partition Pluvier dor? 2012 - 2016 Coordonn?es GPS Lambert 93. 12118 records from Soil metagenome from healthy and unhealthy agricultural soil. 3 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 46 records from Revision of the Garra species of the Hajar Mountains in Oman and the United Arab Emirates with the description of two new species (Teleostei: Cyprinidae). 12457 records from Brown University Herbarium. 103 records from Collection botanique Lamy de la Chapelle E. (BOUM). 875 records from Caracterizaci?n biol?gica de la ventana de biodiversidad Montes de Mar?a, Municipio de Colos?, Sucre, Colombia. 89 records from Donn?es du/de la naturaliste Le baron Gaetan provenant de la base de donn?e du SINP ?le-de-France CETTIA. 19339 records from Inventaire de la flore des Pyr?n?es-Atlantiques 2017 - Littoral. 95 records from BIRDRACE accipiter hardcore birding. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 89 records from Occurrence of mammalia relicts at site Spitzbubenh?hle. 23 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 1 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 17 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 1 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 712 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 2173 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 14 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 136 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 24 records from RNF - Donn?es de la R?serve Naturelle du Marais de Lavours. 1477 records from Inventaire des esp?ces v?g?tales productives dans les Syst?mes Agro-forestiers aux alentours de la For?t class?e de Ziama en Guin?e Foresti?re (BID-AF2015-0066-REG). 140 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A. 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 201 records from Biodiversity of springs and rock seepages 2003. 10776 records from CEFS_16S_ITS. 11 records from Inventaire et regroupement de donn?es Natura 2000. 1198 records from Actualizaci?n de la base de datos de crust?ceos y registro de datos de peces del pac?fico mexicano de la Colecci?n Biol?gica de la Secretar?a de Marina (Peces). 14 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 8 records from Revision of the endemic Philippine Poeciloterpa St?l (Hemiptera: Cercopidae) with description of four new species. 521 records from Schanzenanlage Bergham. 140 records from Planktic foraminifera abundance of Hole 37-332. 74 records from Reptiles de la expedici?n al R?o Apaporis - Proyecto Colombia BIO. 1862 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C. 170 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 98 records from Total foraminifera counts of multinet POS231/3_MSN1332. 1012 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 25 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 603 records from Nannofossil abundance of Hole 37-334. 59 records from Schulgel?nde SGD/Viersen. 1533 records from Donn?es du/de la naturaliste ARNABOLDI Fr?d?ric provenant de la base de donn?e du SINP ?le-de-France CETTIA. 69 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1293 records from Flora gen?rica de las gram?neas del estado de Tlaxcala. 6387 records from Donn?es naturalistes de Monsieur LAFAGE Denis. 103 records from Coccoliths in sediment core GIK23065-3. 5 records from On the genera Ptiloneura Enderlein, Loneura Nav?s, and Loneuroides Garc?a Aldrete (Psocodea: ? Psocoptera?: Ptiloneuridae). 708 records from EDP Baixo Sabor: Herpetology ? Baseline Studies [2009]. 133 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 90 records from Actualizaci?n de la base de datos de la Colecci?n nacional mexicana de cultivos microbianos. 2141 records from University of Amsterdam (NL) - P?ramo Vegetation Research, National Natural Park El Cocuy, Colombia. 23675 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 23 records from Analyses of the recent components of sediment core PS1219-1. 351 records from HBRG Invasive Non-native Plants Dataset. 253 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 3240 records from Inventario flor?stico de la Sierra de Huautla, Morelos. 1 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 186670 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 35 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Par?, Brazil. 16253 records from Birds Specimens. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 468 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : donn?es esp?ces non cibles pi?g?es. 56 records from Planktic foraminifera abundance of Hole 23-227. 17771 records from DMNS Mammal Collection (Arctos). 43 records from (Table 9) Biological parameters of stratigraphic horizons in Core AMK7-734 according to foraminifera. 1 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 1028 records from IBF Monitoring of Fungi. 1 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 4 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 2380 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 1809 records from BenthosChukchiFN762_1976_Falk5. 1118 records from Fig. 4. Pollen record of profile SAO1 (Analyst: J. Hahne). 1 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 89 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 70 records from Donn?es 2017 de l'Observatoire de la Biodiversit? des For?ts. 3238 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 240 records from Knechtweide (Kohlfurth). 19 records from Benthic macrofauna abundance of sediment core 12930-073. 90 records from MCP-Mamiferos - Cole??o de Mam?feros. 582 records from Stable isotope data and sedimentology of core SO42-74KL. 89 records from Meniscus Midges (Dixidae) of Ireland. 1748 records from Occurrence database of native plants and animals of south-central Chile. 342 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 259 records from Natura 2000 Parc naturel r?gional de Lorraine. 3 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 2 records from Hangzhou-sediment-sample Raw sequence reads. 213 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 6 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 264 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 2 records from More cautionary tales: family, generic and species synonymies of recently published taxa of ghost and mud shrimps (Decapoda: Axiidea and Gebiidea). 2271 records from Helmintos par?sitos de peces del sureste de M?xico. 383 records from Inventario de Peces del SFF Isla Malpelo, Proyecto Colombia Bio. 1 records from Two new species of Plutomurus Yosii (Collembola, Tomoceridae) from the Caucasus. 63 records from Total foraminifera counts of multinet M21/4_MSN706. 3 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 81 records from BCCM/ULC Cyanobacteria culture collection at the University of Li?ge (ISO9001 certified). 7 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 353 records from Donn?es naturalistes de Hubert GUIMIER. 1800 records from Donn?es de la collection Rousset -1947-2013. 399 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A. 874 records from Programme ACT : R?partition Grive musicienne 2004 - 2008 Coordonn?es GPS Lambert 93. 134 records from Lynx 2005 pr?sence Occasionnelle Mailles 10km R?seau Loup-Lynx ONCFS. 87 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 154 records from Planktic foraminifera assemblage in sediment core GIK23065-2. 1 records from Schulman's Neotropical Adelobotrys database. 12094 records from Amino acid addition experiment Metagenome. 3131 records from Donn?es DREAL Centre-Val de Loire - Faune - 2018. 45762 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 2 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 9349 records from Harriet Irving Botanical Gardens (HIBG). 46092 records from Weed and native flora data for the Swan Coastal Plain. 99 records from Total foraminifera counts from M35/1_MSN1061. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 9002 records from Uncultured Environmental Isolate Targeted loci environmental. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 1968 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A. 3079 records from Insectes Hym?nopt?res Scollid?s de France. 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 4717 records from Weddell Sea macrozoobenthos EASIZ I. 1345 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 916 records from IOW Natural History & Archaeological Society Marine Records. 13 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 6189 records from Fauna y flora en ?reas con cultivos de palma de aceite en el norte y oriente de Colombia. 14 records from Occurrence of mammalia relicts at site Climauti II. 152 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 135 records from Waldi-Weiher. 4 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingm?hle. 25 records from Donn?es de NICOLAS Vincent (SAPROX). 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 493 records from Fauna and population of oribatid mites (Acari, Oribatida) in the vicinity of Kosogorsky metal works (Tula Region, Russia). 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 1 records from Rhopalomenia glandulosa spec. nov., and the restoration of Entonomenia Leloup (Mollusca: Solenogastres). 6440 records from Microbial ecology of bacteiral community in sediment from adjacent waters of Rushan Bay. 80 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A. 38 records from Phytoplankton counted on two fractions of surface sediment samples from stations B-5 to B-47. 30 records from Planktic foraminifera abundance of Hole 14-144. 2572 records from seawater metagenome Metagenome. 364 records from (Table 10) Distribution of coccoliths in Core AMK7-734 from the Tajura Rift. 4372 records from Heliconiine Butterfly Collection Records from University of Cambridge. 800 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 943 records from Programme ACT : R?partition Tourterelle turque 2012 - 2016 Coordonn?es GPS Lambert 93. 12 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 255 records from Tejidos colectados en el p?ramo de Pisba, Boyac? - Proyecto Boyac? BIO. 79 records from Birdrace-Bielefinken-Bielefeld. 132 records from Range table from ostracoda in ODP Hole 143-866B. 4054 records from Fish specimens of Toyama Science Museum. 6004 records from Colecci?n Limnol?gica Universidad de Antioquia. 146 records from Birdrace-Wannacks_Topti(c)ker-L?beck. 140748 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 4 records from Pheronema on the mid-Atlantic Ridge, data from NRCan. 3529 records from A dataset from bottom trawl survey around Taiwan. 3 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 8 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 1998. 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 230 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 5 records from Copepoda (Siphonostomatoida: Dirivultidae) from Hydrothermal Vent Fields on the Central Indian Ridge, Indian Ocean. 14 records from (Table 4b) Biomass of Emiliania huxleyi and its role in total biomass of phytoplankton along the section from the Pribilofs Islands to the Nunivak Island on 24-25 August 2001. 12 records from Lepidoptera specimen database of Japan. 29 records from Reptiles Specimens of Akita Prefectural Museum. 338 records from UWIZM Snakes. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 182 records from Tejidos colectados en el piedemonte llanero, Boyac? - Proyecto Boyac? BIO. 145 records from Biodiversity survey of Rugezi wetland, Year 2013. 449 records from Artsprosjekt Pyrenomycetes. 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 75152 records from NOAA coral reef monitoring benthic data from sites across Micronesia from 2009-09-29 to 2015-09-25. 121 records from Etude ?cologique du Parc des Lilas (94). 12 records from Donn?es bibliographiques ASFRA. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 7953 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 1 records from A new Aceria species (Acari: Prostigmata: Eriophyoidea) from Minuartia frutescens (Caryophyllaceae) in Hungary. 24 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 7510 records from Base de datos de las gram?neas (Poaceae) del noreste de M?xico. 380 records from UWYMV Herpetology Collection (Arctos). 254 records from Atlantic Forestry Centre Insect Reference Collection. 4036 records from Inventario de larvas de peces en la regi?n sur del Golfo de California (GAP 81, 85 y 86) y en el Pac?fico Tropical Mexicano (GAP 88-91). 14069 records from Midden-Limburg Fish Ponds Survey. 3 records from A new species of Flavoperla Chu, 1929 (Plecoptera: Perlidae) from Guangxi Zhuang Autonomous Region of southern China. 4722 records from Dataflos. 9 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 2743 records from marine sediment metagenome Raw sequence reads. 54593 records from Herbarium Senckenbergianum (FR) - Fungi. 1994 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 ?m fraction. 179 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 5 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 247 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325. 2136 records from (Table 1) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 74-525A from the Walvis Ridge, South Atlantic Ocean. 55 records from Occurrence of mammalia relicts at site Rusenschlo?. 895 records from Geometridae de France m?tropolitaine. 75 records from Plasm bearing foraminifera counts of multinet M21/5_MSN730. 9 records from Benthic macrofauna abundance of sediment core 12930-048. 98 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1381. 1211 records from Tejidos de ejemplares colectados en el P?ramo de Chingaza - Proyecto Colombia Bio. 18 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 203 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 11 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 48 records from Content of coarse fraction and G. menardii in sediment corev V25-44. 276 records from (Table 6) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-216. 675 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 1 records from A new, peculiar genus of Cossoninae (Coleoptera, Curculionidae) from Oman with description of a new species, larva and notes on biology. 7 records from Artenerhebung im Wiesenlautersystem/Pf?lzerwald. 5464 records from Natural History Museum Maastricht (NL) - Herbarium. 9384 records from MZL Invertebrate Collections. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio S?o Francisco basin, southeastern Brazil. 352 records from Loup 2015 pr?sence occasionnelle communale (r?seau Loup-Lynx ONCFS). 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 11 records from Review of the genus Prays H?bner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 170 records from Total foraminifera counts of multinet SO117_MSN1244. 485 records from Rothschild Giraffe occurrence records observed at Mwea National Reserve in Central part of Kenya. 8956 records from Formaci?n de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 6 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 6990 records from Ethnobotanical surveys species in Benin (West Africa). 136 records from Inventaire faunistique de l'ENS des Parc des berges de Seine. 3 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 5576 records from uncultured prokaryote Targeted loci environmental. 3435 records from Benthos Chirnov Basin 1986 and 2002. 6 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 40738 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 15251 records from Universidad Aut?noma de Madrid, Madrid; Lepid?pteros. 1 records from Diversity of methyl alkyl succinate synthase genes in hydrocarbon seep sediments (Raw sequence reads). 1 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 5406 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 1 records from Labrys khuzestanensis n. sp. (Nematoda, Tylenchidae), a new member of the genus with large labial plate. 13 records from Lane 6 Analysis. 10354 records from Inventaire de la flore de Charente-Maritime 2018. 3939 records from Census of plant species in Pahou forest reserve. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 12 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 2043 records from Pollen profile RAC20, Lake Racou, France. 3 records from A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia). 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 10283 records from Inventario de Hymen?ptera; paras?tica en M?xico. 378 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 8561 records from Colecci?n de insectos agr?colas del proyecto diversidad en sistemas de cultivos. 6578 records from Ibaraki Nature Museum, Fungi collection. 1785 records from 3Soil16S. 911 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 190 records from Relative abundance of ostracods in sediment core Sv09. 781 records from Ecological study of the plankton in the port of Ostend in 1965. 715 records from Museu Valenci? d?Hist?ria Natural - Fundaci?n Entomol?gica Torres Sala: FETS. 230 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 93324 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 14 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 49 records from Atelier Malacologie continentale, 14-15septembre, La Fl?che (Sarthe). CEN Pays de la Loire. 23 records from Nannofossil abundance of Hole 24-233A. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 55 records from Dinoflagellate abundance of Hole 28-274. 50 records from Occurrence of mammalia relicts at site Biedermann. 20442 records from Trondheim urban biodyversity survey. 94 records from Donn?es du/de la naturaliste LUSTRAT Philippe provenant de la base de donn?e du SINP ?le-de-France CETTIA. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 323 records from Size of planktic foraminifera at CTD station PS55/083-1. 58 records from Swedish Malaise Trap Project (SMTP) - Banchini. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 312 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 23136 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 34508 records from R. L. McGregor Herbarium Lichen Collection. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 27670 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 12 records from A revision of the spider genus Anemesia (Araneae, Cyrtaucheniidae). 47 records from Distribuci?n de la Nutria (Lontra longicaudis) en la cuenca baja del r?o Sin? en el departamento de C?rdoba. 516 records from Planktic foraminifera counts of sediment core A15-558. 276 records from Birds Specimens of Akita Prefectural Museum. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 217 records from Cole??o de Bryozoa do Museu Nacional - UFRJ. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 100 records from Donn?es naturalistes de LE GLOANEC Vincent. 117837 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-71, 1974-5. 370 records from Size of planktic foraminifera at CTD station PS55/051. 16 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 869 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 557 records from Corn bunting breeding distribution in Scotland. 7122 records from Whale catches in the Southern Ocean. 919 records from Cole??o Zool?gica de Refer?ncia da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 69 records from Foraminifera species abundances from tow TT007_7-MOC13. 336 records from KARSTLANDSCHAFT S?DHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am R?seberg). 4 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 2 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 40011 records from Banded Iron Formation and Greenstone survey data. 28 records from Microzooplankton abundance and biomass at station TT045_19-3. 75 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 91 records from Anfibios y reptiles de sistemas c?rsticos en el municipio de El Pe??n, Santander - Proyecto Colombia BIO. 13868 records from Donn?es faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-V?gel (VFV). 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 118 records from Observation des insectes sur le territoire de la M?tropole Rouen Normandie. 1148 records from ABC event data for Nyika Plateau, Buma Hills. 16 records from Hazel Dormouse in Ireland. 106 records from Distribution of planktic foraminifera (125-250 ?m) of box sediment core PS1246-2. 145 records from Range table from planktonic foraminifers in ODP Hole 167-1021B. 285 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 55 records from Macroinvertebrados bent?nicos de playas de arena (Monte Hermoso-Pehuen C?, Buenos Aires, Argentina). 1027 records from Programme ACT : R?partition Merle noir 1996 - 2000 Coordonn?es GPS Lambert 93. 7 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 123 records from Total foraminifera counts of multinet M21/4_MSN694. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 5978 records from (Table 1) Ranges of Paleocene to middle Eocene planktonic foraminifera in ODP Hole 119-738B. 119 records from Suivi des leucorrines sur le site du Marais du Plata. 46 records from An der Ohm, (Wettsaasen). 49 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 185 records from Inventaire des odonates d'int?r?t communautaire. 149 records from Restauraci?n de flora y repoblamiento de fauna nativa en 1,000 hect?reas para el restablecimiento del corredor biol?gico costero en la Laguna Madre, Tamaulipas. 127 records from ?ypripedium guttatum Sw. in the Komi republic. 1893 records from Donn?es de la collection de Hubert Piguet - Famille des Elateridae. 2419 records from Flora de las sabanas inundables de las cuencas de los r?os Bita, Manacac?as y Cravo Sur - SULU II. 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 118 records from Radiolaria assemblage in sediment core GIK23400-3. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 877 records from Range table from benthic foraminifers in ODP Hole 151-913B. 216 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 148 records from Abundance of birds in the Lena Delta Region. 259 records from Programme ACT : R?partition Alouette lulu 2009 - 2013 Coordonn?es GPS Lambert 93. 95 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 32 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 433 records from Synth?se de la R?partition des populations de chamois en 1988 (r?seau Ongul?s sauvages ONCFS-FNC-FDC). 2102 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 124 records from Kirkliston Range stream monitoring. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 3 records from Museo Provincial de Ciencias Naturales ?Florentino Ameghino?, Santa Fe, Argentina - Colecci?n Squamata (no Serpentes) (MFA-ZV-Sq). 381 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 35 records from Ortsrand Zandershagen. 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 39 records from Planktic foraminifera counts of sediment core V19-21. 2420 records from (Figure 10) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-631A. 1 records from Occurrence of mammalia relicts at site Ballybetagh. 16838 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 5360 records from Colecci?n Ornitol?gica de la Universidad del Valle. 7839 records from Inventario flor?stico de la regi?n Calakmul-parte baja de la regi?n Lacandona (Cuenca alta del Usumacinta y Marqu?s de Comillas). 294817 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations. 43 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 130 records from BIRDRACE - The famous Grouse feat. The James. 374 records from Planktic foraminifera abundance of Hole 68-503B. 63 records from Distribution of meiofauna in surface sediments of the Iberian deep sea basin (Table 3). 294 records from Aves de la expedici?n en el p?ramo El Valle, Boyac? - Proyecto Boyac? BIO. 26 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 ?m. 552 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 5 records from Three?new country records from the genus?Limnephilus?Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 1 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper R?o Magdalena, Colombia. 6 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 74 records from Anfibiofauna asociada a la quebrada Giginia, corregimiento de Do?a Josefa, Municipio del Atrato - Choc?, 2019. 52 records from Occurrence of mammalia relicts at site Goyet Cave 3. 37 records from FBIP: scallop population genetics. 18 records from Schulgarten der Gesamtschule Am Heidberg. 1270 records from Donn?es du/de la naturaliste Lantz Andr? provenant de la base de donn?e du SINP ?le-de-France CETTIA. 70 records from Gew?sser des Wartbergparks Stuttgart (bei der ?kostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 5496 records from Abondances et caract?ristiques biologiques des juv?niles de saumons ?chantillonn?s lors des indices d'abondance du saumon dans la rivi?re Nivelle (France). 62 records from Donn?es naturalistes de BONCHE J?r?me. 36 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 ?m fraction. 304 records from Base de datos de fauna batial, abisopel?gica y abisal del Golfo de M?xico. 79758 records from natagora-earlybirds. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 8985 records from Universidad de Murcia, Dpto. Biolog?a Vegetal (Bot?nica), Murcia: MUB-MUSCI. 20 records from Range table from planktonic foraminifers in ODP Hole 167-1010B. 5538 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 338 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Privolzhskaya Lesostep. 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 10 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 1 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 188 records from Donn?es de Mammif?res marins. Mission Sanctuaire AGOA de 2012 ? 2014. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 852 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 1 records from First record of the genus Chandleriella Hlav?? (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 324 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-017. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 181 records from Total foraminifera counts from multinet M31/3_MSN915. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 41676 records from Tagged Seal Location Data from SOGLOBEC. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 6 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 333 records from Donn?es naturalistes de Renaud PUISSAUVE. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 946 records from Pollen analysis of sediment profile HAE10 from H?melsee. 1 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 1709 records from The Gibson spider collection. 56 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 10766 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 195 records from Truppen?bungsplatz Panzerkaserne B?blingen. 1256 records from (Fig. 1) Ice rafted debris and planktic foraminifers of Hole 94-609. 651 records from R?seaux ?cologiques/Trame verte et bleue. 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 14 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 19 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 4 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 66164 records from Florida Keys Reef Visual Census 1996. 20 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 68910 records from Donn?es de l'Observatoire de la Faune de Bourgogne. 1184 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 255 records from Programme ACT : R?partition Perdrix rouge 2009 - 2013 Coordonn?es GPS Lambert 93. 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 4389 records from Colecci?n Herpetol?gica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 236480 records from Wild bees of Belgium. 5 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 54 records from Donn?es du/de la naturaliste Villalta R?mi provenant de la base de donn?e du SINP ?le-de-France CETTIA. 22 records from Observations de tortues marines dans l'archipel de Saint-Pierre et Miquelon. 539 records from Phenological Center - Birds (Murmansk). 9 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 100 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from R?o Ventuari, Venezuela. 187 records from Museu de Ci?ncies Naturals de Barcelona: MCNB-Tissue. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 309 records from Echinoderms from the Seaflower Biosphere Reserve. 300 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 198 records from Programme ACT : R?partition Alouette lulu 1996 - 2000 Coordonn?es GPS Lambert 93. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 1450 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 218 records from Nannofossil abundance of Hole 49-408. 874 records from (Table 1) Calcareous nannofossil distribution and relative abundance in ODP Hole 114-699A. 23 records from Analyses of the recent components of sediment core PS1011-1. 48 records from Total foraminifera counts of multinet M6/7_MSN140. 9740 records from Royal British Columbia Museum Entomology Collection. 24 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 106 records from Dinoflagellate abundance of Hole 81-552. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 28 records from MVZ Herp Observations (Arctos). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 2800 records from Mid-Pleistocene (800-400 ka) planktic foraminfer assemblages of IODP Site 306-U1314. 8 records from A review of the Neotropical microcaddisfly genus Acostatrichia Mosely, 1939 with description of a new species from Brazil (Trichoptera: Hydroptilidae: Leucotrichiinae). 5938 records from Plan Am?nagement et de Gestion Simplifi? (PAGS) des for?ts galeries des d?partements de l'Ou?m?-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 25 records from Inventario de Murci?lagos Buenos Aires, Tauramena, Casanare. 6 records from Foraminifera abundance of Hole 58-442. 8367 records from Aves Acu?ticas de las sabanas inundables del Meta y Casanare. 177 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 3 records from Denitrification bacteria in sediment cores of Daya Bay, China. 5 records from Thoridae (Crustacea: Decapoda) can penetrate the Abyss: a new species of Lebbeus from the Sea of Okhotsk, representing the deepest record of the family. 6 records from Five new species of Nazeris Fauvel in Guangxi, China (Coleoptera, Staphylinidae, Paederinae). 5 records from Donn?es naturalistes de Mika?l PAILLET. 4607 records from Donn?es de type contact en Guadeloupe. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 351600 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 922 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 79 records from New records of Ichneumonidae (Hymenoptera) for the Italian fauna. 186 records from Benthic foraminifera and algae abundance of Hole 81-554. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_5-CTD58. 136 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 36 records from Planktic foraminifera assemblage in sediment core GIK23243-2. 55 records from Galls on Beech Trees in Hainich, 2008. 6 records from New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae) from Colombia, with an identification key for all known species of the genus. 243726 records from Carnet B Lorraine. 31 records from Ecosystems of the sandstone region incl. sand-belt (SE of Melb.). 27 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 8 records from A new species of Cetopsis from the Guiana Shield (Siluriformes: Cetopsidae: Cetopsinae). 346979 records from Seasearch Marine Surveys in England. 38 records from Planktic foraminifera abundance of Hole 84-566C. 640 records from Annales de la Soci?t? Linn?enne de Maine-et-Loire. 9 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 2290 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 2963 records from Collection Trichoptera - SMF. 12451 records from Insectes H?t?ropt?res Mirides de France. 16 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 3 records from Taxonomic notes on the tribe Dryptini Bonelli, 1810 with description of a new genus and species from China (Coleoptera: Carabidae: Dryptini). 354 records from Programme ACT : R?partition Caille des bl?s 2000 - 2004 Coordonn?es GPS Lambert 93. 701 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 3740 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 749 records from Pollen analysis of sediment core GeoB6518-1. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 798 records from Planktic foraminifera abundance of Hole 27-262. 494194 records from BLS Mapping Scheme dataset, 1750-2009. 107742 records from Arizona State University Hasbrouck Insect Collection. 39 records from Planktic foraminifera abundance of Hole 27-260. 1114 records from Chronicle of Nature - Phenology of Plants of Kronotsky Federal Nature Biosphere Reserve. 94 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 124 records from Birdrace-Die_Ackerm?nnchen-Schalm-Eder-Kreis. 3361 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetol?gica Chetumal). 35 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 10 records from New plant associations for adults of some species of Acmaeodera Eschscholtz (Coleoptera: Buprestidae) occurring in the western United States. 1480 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 1 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 53 records from Donn?es du/de la naturaliste Dubois Yves provenant de la base de donn?e du SINP ?le-de-France CETTIA. 30 records from Feral Pigs - Sightings and Cull records - 2014-2015. 131 records from Occurrence of mammalia relicts at site Bocksteinschmiede. 91 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 130 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 18 records from Anfibios presentes en el Cerro J?nano. 120 records from Donn?es esp?ces - Expertise IPE 79. 1715185 records from NBIS Records to December 2016. 27 records from Planktic foraminifera abundance of Hole 51-417B. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 53 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 18 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 2859 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 39 records from Range table from planktonic foraminifers in ODP Hole 178-1096A. 931 records from South American Antarctic Marine Biodiversity Literature. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 81 records from M?tropole_Nice_C?te_d'Azur_2017_12_18. 5 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 1894 records from Fungi Collection. 49 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 1001 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 2 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 87 records from Donn?es esp?ces - Expertise IPE 70. 12 records from Two new genera and three new subterranean species of Hydrobiidae (Caenogastropoda: Truncatelloidea) from Tunisia. 1028 records from NOAA coral reef monitoring invertebrate data from sites across Micronesia from 2009-09-29 to 2015-09-25. 1930 records from Donn?es de la naturaliste Lemoine Delphine provenant de la base de donn?e du SINP ?le-de-France CETTIA. 17 records from Thirteen new records of ferns from Brazil. 713 records from Modelaci?n de la distribuci?n y abundancia de las subespecies de venado cola blanca en M?xico: implicaciones de conservaci?n y manejo. 384 records from Marine metagenome ICM_AWP. 3580 records from The reptiles and amphibians collection (RA) of the Mus?um national d'Histoire Naturelle (MNHN - Paris). 4 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 121 records from Foraminifera abundance of sediment core IN68-28. 20 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 3 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 30954 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 179 records from Plasm bearing foraminifera counts from multinet SO119_MSN1281. 121 records from Total foraminifera counts of multinet M10/2_MSN262. 2 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 98 records from Description of lithologic section units of IODP Hole 325-M0033A. 21 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 46 records from Total foraminifera counts of multinet M21/5_MSN742. 67 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 6322 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, M?xico. 350 records from Orchideenstandort Nostengraben - Kretzberg (O?maritz). 98 records from Donn?es opportunistes sur les odonates. 282 records from Deponie Klausdorf. 48 records from Schulgel?nde (Wetter). 14980 records from Donn?es Entomologiques A. HORELLOU 1988-2018. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 285 records from Donn?es du/de la naturaliste Cousin Richard provenant de la base de donn?e du SINP ?le-de-France CETTIA. 558 records from Foraminifera abundance of Hole 74-526A. 61 records from Phytoplankton abundance at station Casma_2003-04-28_2, Casma, Peru. 22800 records from Floristische Kartierung ?sterreichs - Mapping the Flora of Austria. 48 records from ZUEC-ECH - Cole??o de Echinoidea do Museu de Zoologia da UNICAMP. 56582 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 1986 records from Observations de Col?opt?res saproxyliques de Fr?d?ric LACOSTE. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis H?bner (Lepidoptera: Tortricidae). 2 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 31 records from Benthic foraminifera abundance of Hole 42-379A. 1489 records from Population research on small rodents (Rodentia) and screws (Soridae) in Steinkjer Municipality ? Norway; 2018 - 2019 based on systematic catches with ordinary mouse traps in traplines. 1462 records from (Table 3) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-657A. 600 records from Colecci?n de Herpetolog?a de la Universidad del Quind?o (HERPETOS-UQ). 2548 records from BioGIS - Reptiles - HUJ collections. 13 records from Analyses of the recent components of sediment core PS1222-1. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 237 records from Planktic foraminifera abundance of Hole 21-207. 768925 records from Flora Atlas N.T.. 12 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 16 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 3 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 203 records from Insectos de la expedici?n al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 18 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 84 records from Ostracoda abundance of Hole 48-403. 2 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 12 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, ?CT scans, drawings and DNA sequence data). 2 records from Two new species of Hetereleotris (Perciformes: Gobiidae) from the Red Sea. 2714 records from Donn?es de la R?serve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donn?e du SINP ?le-de-France CETTIA. 129 records from Donn?es du/de la naturaliste jourdan christian provenant de la base de donn?e du SINP ?le-de-France CETTIA. 147 records from Revision of the spider genus Hoplopholcus Kulczy?ski (Araneae, Pholcidae). 754 records from Programme ACT : R?partition Grive draine 2001 - 2005 Coordonn?es GPS Lambert 93. 1856 records from Analysis of macrobenthos in the Southern Bight of the North Sea (1971-1972). 94 records from Caddisflies (Insecta: Trichoptera) from Maranh?o State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 990 records from Colecci?n base (BGVPA) del Banco de germoplasma del Jard?n Bot?nico Atl?ntico de Gij?n. 10 records from Ostracoda abundance of Hole 32-306. 656 records from Nannofossil abundance of Hole 29-281. 3856 records from Proyecto interno ejecutado por la CONABIO: Sistema de informaci?n sobre Bosque Mes?filo de Monta?a de M?xico para apoyo en programas de restauraci?n (Fase 1). 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 315 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 14 records from Range table from planktonic foraminifers in ODP Hole 139-856C. 580 records from Rare plants database extract from Scottish Natural Heritage. 2497 records from Donn?es des collections d'algues du MNHN. 76 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 2253 records from SP-Algae - Herb?rio do Estado "Maria Eneyda P. Kaufmann Fidalgo - Cole??o de Algas. 68396 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 27220 records from Formidabel; Belgian Ants Database. 3272 records from Mammif?res marins Guadeloupe Antilles fran?aises (AET). Suppl?ments. 53 records from Relative abundance of planktic foraminifera in sediment core K11. 27 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 697 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 457 records from Helmintos par?sitos de peces dulceacu?colas de cuencas hidrol?gicas del Centro-Norte de M?xico (Durango). 275 records from Composici?n flor?stica de ?reas degradadas por actividad minera a cielo abierto en el municipio de Condoto-Choc?, como insumo para calcular la biomasa vegetal, 2017. 87901 records from MDFRC macroinvertebrate survey. 1 records from Planktic foraminifera abundance of Hole 54-420A. 128 records from Inventaire des reptiles 2014. 40135 records from DIBA-Parc del Montnegre i el Corredor. 21 records from Caracterizaci?n de la epifauna y macrobentos (0-800 m) de Isla Cayo Serranilla y ?reas aleda?as: Equinodermos primera fase 2017 - Proyecto Colombia Bio. 4755 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 1 records from Re-description of Grammapsychops lebedevi Martynova, 1954 (Neuroptera: Psychopsidae) with notes on the Late Cretaceous psychopsoids. 589 records from Programme ACT : R?partition Pie bavarde 2005 - 2009 Coordonn?es GPS Lambert 93. 53 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 29412 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 53 records from Description of lithologic section units of IODP Hole 325-M0043A. 7 records from Grundwasserlebensraum im Englischen Garten (M?nchen). 1993 records from Inventario de macroalgas de Isla Guadalupe, M?xico. 213 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 830 records from Invertebrados del Parque Nacional Arrecife Puerto Morelos. 19 records from Nesting biology and distribution of Stenancistrocerus (Paratropancistrocerus) obstrictus (Morawitz, 1895) (Hymenoptera: Vespidae: Eumeninae). 151 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 7896 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung M?nchen. 9476 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 20440 records from Inventaire de la flore de Charente-Maritime 2017. 2873 records from Colecci?n Thomas G. Zoebisch asociada a la Colecci?n Entomol?gica del Centro de Estudios en Zoolog?a (Mexicanos). 3 records from Prosoglypta, a new remarkable genus from Vietnam (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 720 records from Donn?es du naturaliste Bussac Augustin provenant de la base de donn?e du SINP ?le-de-France CETTIA. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 4853 records from Inventaire des esp?ces v?g?tales du sous bois des plantations de Teck de la for?t naturelle de la Lama. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 983 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 411 records from SuLaMa reptile survey I 2012. 61 records from Shrews of Poland. 40 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 9 records from Nannofossil abundance of Hole 2-11. 2 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 44050 records from Donn?es naturalistes de Pascal Dupont. 18 records from suivi du site Natura 2000 Carri?re Saint Nicolas. 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 130 records from Faunal assemblage of sediment core GS7603-13. 2170 records from Inventaire des sangsues - d?termination pr?l?vements de bureau d'?tudes (qualit? de l'eau) - Subvention UMS Patrinat. 271 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0012A. 2405 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 186 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 19 records from Nannofossil abundance of Hole 6-48B. 2 records from Wie viel Natur gibt es im Park?. 1764 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 2 records from A new species of the fishfly genus Neochauliodes van der Weele (Megaloptera Corydalidae) from India. 181700 records from Marine benthic dataset (version 1) commissioned by UKOOA. 5229 records from European Moth Nights. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 172 records from Donn?es du/de la naturaliste Roquinarc'h Oc?ane provenant de la base de donn?e du SINP ?le-de-France CETTIA. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 1082 records from Zootaxa. 2297 records from Colecci?n de Anfibios. 6775 records from Donn?es du naturaliste MIGUET Pierre provenant de la base de donn?e du SINP ?le-de-France CETTIA. 10979 records from NBMB Herps. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 386 records from Foraminifera distribution of sediment core KS310. 1462 records from Colecta bot?nica: ?rea maya regi?n de la Reserva Calakmul, Campeche. 11131 records from Efectos del Cambio Ambiental en las comunidades de organismos de los r?os mediterr?neos. 3018 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 170 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 2970 records from Distribution patterns of subtidal macrobenthos in the Tsitsikamma National Park. 1036 records from BUND - Dassower See (L?beck/Dassow). 102 records from (Table 3) Abundance and biomass of Proboscia alata in patches of its mass development over the Bering Sea middle shelf, percentages of P. alata and associated algae species and their groups in total phytoplankton abundance and biomass. 59978 records from Donn?es naturalistes de Monsieur Fran?ois FOURNIER. 405 records from NHMO DNA Bank Other groups collection. 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 531 records from Fish biodiversity of the Vit?ria-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 54016 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 27676 records from Insect Collection from the Museu Nacional de Hist?ria Natural e da Ci?ncia, Universidade de Lisboa, Portugal. 12 records from Analyses of the recent components in the sand fraction of sediment core PS1012-1. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 32 records from Nanoplankton abundance at station GeoB2012-5. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 368 records from Ring ouzel national sample survey in the UK in 1999. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 841 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 7484 records from Yoann_BLANCHON_2017_12_18. 250 records from Inventaire et regroupement de donn?es Natura 2000. 64 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 1 records from Notes on the genus Gargela (Lepidoptera: Crambidae) ? with descriptions of two new species from China. 12719 records from Donn?es bibliographiques et opportunistes Mammif?res du Nord Pas-de-Calais issues du SIRF. 637617 records from Donn?es de la flore d?Alsace (SBA). 1012 records from Programme ACT : R?partition Merle noir 2000 - 2004. 3 records from MSB Mammal Observations (Arctos). 490 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 2 records from Pygmy grasshoppers of the genus Formosatettix Tinkham? 1937 (Orthoptera: Tetrigidae: Tetriginae). 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 10 records from Donn?es naturalistes de Sophie COHEN. 2126593 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 696 records from the diversity of anammox bacteria in the subterranean estuary. 60 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB03 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 380 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 26185 records from Donn?es Mammif?res Midi-Pyr?n?es enregistr?es dans BazNat - Lot 1. 20068 records from Wikiplantbase #Sicilia. 2 records from The spider wasp genus Telostholus Haupt, 1929 (Hymenoptera, Pompilidae) in Malaysia, with the description of four new species. 1176 records from Nannofossil abundance of Hole 17-167. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 176 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 2499 records from Database of Australasian Vertebrate Occurrences. 498 records from Bekkelag basin, Inner Oslofjord. 215 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 4 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 748 records from Phenological Center - Birds (Laplandskiy). 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 551 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 681 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1994. 57 records from Inventaire faune flore de l'?tang d'Abbecourt ? Orgeval. 62 records from Benthic foraminifera abundance of Hole 42-380. 110497 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 423 records from Programme ACT : R?partition Caille des bl?s 2008 - 2012 Coordonn?es GPS Lambert 93. 1010731 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 163 records from (Table 2) Palynomorph concentrations in ODP Hole 105-647A samples. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 57 records from Composition of the smaller coarse silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 143 records from Agromyzidae (Diptera: Schizophora) in the state of Par?: new species and new records in Brazil. 6 records from NZCS Invertebrates New Collection After 1987. 2985 records from Colecci?n Entomol?gica CDMB. 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 16929 records from Lepidoptera (Specimens NRM). 13 records from Cole??o de Coleoptera da Universidade de Bras?lia. 440 records from (Table 2) Species composition of algae and cyanobacteria encountered in plankton of the Large Aral Sea on June 2-8, 2008. 98 records from Warnowtal (Rostock). 198 records from Chronicle of Nature - Phenology of Birds of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 822 records from Las comunidades de myxomicetes de selva baja caducifolia. 26 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 2 records from C?digo de barras de ejemplares de la Colecci?n Nacional de Mam?feros del Instituto de Biolog?a, UNAM. 27799 records from Collection of saproxylic and xylobiont Beetles. 2747 records from Compost microbe establishment and growth in agricultural soils. 781 records from Composici?n flor?stica y estructura de tres parcelas permanentes en diferentes estados sucesionales en transici?n de bosques h?medos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 202122 records from National Benthic Inventory. 140 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 16 records from Phenological Center - Fishes (Murmansk). 415 records from Caracterizaci?n de vegetaci?n para el establecimiento de l?mites funcionales de humedales: Ci?naga de la Virgen, Ci?naga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 88 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 22122 records from Tachinid Recording Scheme - GB and Ireland records. 1555478 records from Flore Franco-Belge. 1762 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 16437 records from EAC - Herb?rio Prisco Bezerra. 29105 records from Marine Biological Sample Database, JAMSTEC. 2565 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 330 records from Otter (Lutra lutra), Outer Hebrides. 743 records from Insectos recolectados en trampas Malaise en el departamento de Antioquia - Proyecto Colombia Bio. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1531 records from Leif Richardson Vermont Bee Specimens. 9 records from PRA Sonneur ? ventre jaune - ?tude de r?partition. 63 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 8570 records from Collection Crustacea - ZMB. 874 records from The Living Murray Fish data. 740 records from Estudio herpetofaun?stico de la Sierra Mazateca, Oaxaca, M?xico. 4 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 4428 records from "Categorization of the wild food plants and their importance for primate development in the natural forest of Akpe (Lama) in southern Benin.". 19 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 25974 records from Long-term Bird Census in Cigu 2004-2017. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 7 records from Contribution to the AIrotropical ?chneumoninae (Hymenoptera, ?chneumonidae) Irom Gabon and Sierra Leone, with descriptions oI Iive new species and two new subspecies. 5 records from Range table from planktonic foraminifers in ODP Hole 159-960A. 1128 records from Distribution of foraminiferal fauna from ODP Hole 122-762C (Table 1). 240 records from BARTH-Environnement_2017_12_18. 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 15 records from Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae). 1 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 232 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 493 records from Study of epibenthos and demersal fish in and around the thiocarbamate discharge area of the Belgian Continental Shelf (1977-1981). 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 162 records from Total foraminifera counts of multinet M21/2_MSN658. 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 35 records from Nannofossil abundance of Hole 9-82. 25 records from Microzooplankton abundance and biomass at station TT043_11-1. 1956 records from Colecci?n de Entomolog?a - Hymenoptera - Chalcidoidea. 2654 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 59 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 2327 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 102 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 101 records from BIRDRACE Enger am Spektiv. 79 records from Swedish Malaise Trap Project (SMTP) - Syrphidae. 1377 records from Ghent university - Zoology Museum - Nematod Collection. 32 records from Sciapodinae from the Himalayan region with description of nine new species from Tibet (Diptera: Dolichopodidae). 136 records from Total foraminifera counts from multinet M32/3_MSN956. 114 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 6164 records from Donn?es naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 10 records from Donn?es naturalistes de CLERGET sylvie. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 2 records from A new genus and species of grasshopper from China (Orthoptera: Acrididae Catantopinae). 13 records from Warnowufer Gro? Klein. 7 records from Stadtrandlandschaft Apolda-Nord. 12 records from Microzooplankton abundance and biomass at station NBP97-03-13-2. 153 records from Planktic foraminifera abundance of Hole 18-181. 40 records from Calliostomatidae, Colloniidae, Margaritidae, and Solariellidae (Gastropoda: Trochoidea) collected by the Marion Dufresne (MD 55) expedition in southeastern Brazil, with description of a new species of Calliostoma. 3 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 198 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 1 records from BOTU-Fungi - Herb?rio Irina Delanova Gemtch?jnicov - Cole??o de Fungos. 18540 records from Sistem?tica e historia natural de algunos anfibios y reptiles de M?xico. 5 records from A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from India. 2 records from First description of male of the type species Parosmylus prominens Needham, 1909 (Neuroptera: Osmylidae) from India. 7 records from Notes on slender species of the long-jawed spider genus Tetragnatha (Araneae Tetragnathidae) with description of three new species. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 237 records from Evaluaci?n del ?mbito hogare?o y calidad de h?bitat del borrego cimarr?n (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Bi?sfera El Pinacate y Gran Desierto de Altar. 3304 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 322193 records from Florida Keys Reef Visual Census 2010. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 153 records from annex1. 132 records from Total foraminifera counts of multinet POS247/2_MSN1377. 343 records from Programme ACT : R?partition Caille des bl?s 2012 - 2016 Coordonn?es GPS Lambert 93. 35 records from Dinoflagellate abundance of Hole 28-270. 2 records from Review of Allanagrus Noyes & Valentine (Hymenoptera: Mymaridae) with a key to species. 273 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 564 records from Biological Collection, National Institute of Oceanography, Goa, India. 45367 records from The Environmental Sample Collection of Spiders at the Staatliches Museum f?r Naturkunde Karlsruhe. 134 records from Pollen profile II/B at Krumbach, Germany. 1579 records from Occurrence data set for wild food plant species in Zimbabwe's biodiversity hotspots. 1000 records from ABC_Useful Plants of Malawi: Species used as Herbal aphrodisiacs. 12705 records from Weevil and Bark Beetle Recording Scheme - data verified via iRecord. 93 records from A revision of the genus Mesoconius Enderlein (Diptera, Micropezidae, Taeniapterinae). 51 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 17 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 3795 records from Composici?n flor?stica y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 1067 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 96 records from (Table 3) Abundance of living foraminifers in bottom sediments from the Kandalaksha Bay. 38 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimar?es & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 2 records from Nannofossil abundance of Hole 4-26A. 96 records from Planktic foraminifera abundance of Hole 22-212. 93 records from Donn?es du/de la naturaliste Fourrier Thibault provenant de la base de donn?e du SINP ?le-de-France CETTIA. 45 records from Universit? P?dagogique Nationale de Kinshasa (UPN) - Le b?tail dans la R?publique D?mocratique du Congo (bases de donn?es des animaux ?lev?s pour consommation)- Projet CABIN. 1 records from Planktic foraminifera abundance of Hole 54-428. 282 records from Ichthyofauna of the Kubo, Tochikura, and Ichinono river systems (Kitakami River drainage, northern Japan), with a comparison of predicted and surveyed species richness. 287 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 39 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colecci?n de Peces Dulceacu?colas of Instituto de Investigaci?n de Recursos Biol?gicos Alexander von Humboldt (IAvH-P), Colombia. 1 records from Family, generic and species synonymies of recently published taxa of ghost shrimps (Decapoda, Axiidea, Eucalliacidae and Ctenochelidae): cautionary tales. 21 records from Benthic macrofauna abundance of sediment core 13200-045. 6776 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 2217 records from Monitoreo de la poblaci?n de la guacamaya verde en la Reserva de la Biosfera Tehuac?n-Cuicatl?n. 1054 records from Aves de la cuenca alta y media del r?o Bita, (Vichada) Colombia. 271 records from (Table 3) Occurrence of benthic foraminifers in ODP Hole 116-718C. 86 records from Donn?es naturalistes de Pierre-Alexis RAULT. 60 records from Wichita State University Collection. 2 records from Two new Isotomidae species (Collembola) from Esp?rito Santo State, Brazil. 1 records from The Cat-eyed Snakes of Madagascar: Phylogeny and Description of a New Species of Madagascarophis (Serpentes: Lamprophiidae) from the Tsingy of Ankarana. 2336 records from (App 8) Relative contents of planktonic foraminifera species in sediments from Core GeoB3011-2. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 8158 records from Dark ocean microbial diversity. 2167 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 1 records from A new genus and new species of freshwater crab (Decapoda: Brachyura: Potamidae Ortmann, 1896) from Yunnan Province, China. 10 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 327 records from pbzt_insect_biodiversity. 7 records from Insect specimens of Himeji City Science Museum. 82 records from Bulletin de la Soci?t? Linn?enne de Bordeaux, Tome 148 (N.S) n? 41 (1), 2013 - Donn?es faune. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 2282 records from Ohio University Invertebrate Paleontology Collection. 3477 records from (Table 13) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-591. 2 records from Four new species of Phyllophaga Harris (Coleoptera: Scarabaeidae: Melolonthinae) from western Cuba. 4 records from S?chsische Schweiz (Wehlener Gebiet). 11 records from Barsine insolita, a new species from Indochina and India (Lepidoptera, Erebidae, Arctiinae). 42 records from DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 3 records from El g?nero Aleuroparadoxus Quaintance y Baker 1914, con descripci?n de tres nuevas especies, nuevos registros y clave para las especies (Hemiptera: Aleyrodidae). 2 records from Tepuidessus grulai sp. nov. from Acop?n Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 29 records from Ours 2004 pr?sence Occasionnelle Mailles 10km LAEA R?seau Ours brun ONCFS. 774 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 463 records from Damselflies of the genus Argia (Odonata: Coenagrionidae) from Ecuador with descriptions of five new species. 3 records from Description of Bradinopyga konkanensis sp. nov. (Odonata: Anisoptera Libellulidae) from the coastal region of Maharashtra, India. 192288 records from University of Michigan Museum of Zoology, Division of Birds. 40 records from Planktic foraminifera abundance of Hole 14-137. 2348 records from UWYMV Bird Collection (Arctos). 751 records from Donn?es naturalistes de Monsieur JOURDE R?mi. 811 records from Donn?es naturalistes de AUNEAU Florent. 873 records from Programme ACT : R?partition Geai des ch?nes 2008 - 2012 Coordonn?es GPS Lambert 93. 1806 records from uncultured marine picoeukaryote strain:Peuk_V4_NWP2 Raw sequence reads. 640 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 5 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 42 records from Occurrence of mammalia relicts at site l?Abri de Campalou. 363 records from (App 1) Relative contents of mass species of benthic foraminifera in Holocene sediments from Core ASV11-880-3. 421 records from Collection Graptolithina fossil SMF. 10 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 1146667 records from PlutoF platform observations. 25934 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pac?fico mexicano (costa oeste de Baja California, Pac?fico centro y sur). 10 records from Talitrid amphipods from India, East Africa and the Red Sea (Amphipoda, Senticaudata, Talitroidea, Talitridae). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paran? basin, Brazil. 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 11 records from Suphisellus grossoi sp. n., a new burrowing water beetle from South America and notes on S. flavolineatus (R?gimbart, 1889) and S. grammicus (Sharp, 1882) (Coleoptera: Noteridae). 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 136 records from Total foraminifera counts of multinet M21/6_MSN784. 84 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 129 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 62 records from Zoo Frankfurt. 203 records from Estrategia de conservaci?n de grandes felinos en el departamento del Meta. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 1085517 records from Fungal Records Database of Britain and Ireland. 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 50 records from Nannofossil abundance of Hole 10-89. 31 records from Bulletin d'informations de l'Association fran?aise de Lich?nologie. 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 177 records from Nannofossil abundance of Hole 30-285A. 738 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 237 records from Capercaillie national surveys. 61645 records from La familia Asteraceae en M?xico. Fase VI. 620 records from (Table 3) Protist occurrence in bottom sea ice and surface water samples obtained during a CCGS Amundsen cruise in 2007/2008. 1494 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 23646 records from WTSWW Data: All Taxa (West Wales). 63 records from Marine gastropod distribution from patagonian shallow waters. 128 records from Donn?es esp?ces - Expertise IPE 10. 1 records from Species delimitations in the Atractus collaris complex (Serpentes: Dipsadidae). 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 11 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 19 records from New species of Otiothopinae (Araneae: Palpimanidae) from Colombia. 9 records from Sarcodine counts and carbon biomass at station TT008_6-PMOC7. 203 records from (Abb. 8 bot) Pollen profile Radauerborn, Harz. 69 records from Unter hellen Zinnen und finsteren Grotten. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 1003 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 134 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 6433 records from Modernisation des ZNIEFF du PnrL. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 16 records from Dinoflagellate cysts of surface sediments. 5 records from Collection Malakologie - SMNG. 20 records from Occurrence of mammalia relicts at site Niederlehme. 601 records from Muestreos y recolectas de flora end?mica y casi-end?mica de matorral costero y chaparral de la zona mediterr?nea Baja California, M?xico. 50 records from Donn?es d'observation de phan?rogames marines en Martinique. 1264 records from Grand Voyeux - Suivis scientifiques. 1721 records from Phytoplankton data collected from the Black Sea during November 1957 (Cruise 2). 86 records from UWIZM Cnidarians. 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 374 records from Coastal and Marine Species Database. 190 records from Nannofossil abundance of Hole 67-499. 80 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 900 records from Convention F?d?ration fran?aise de golf - MNHN 2016-2019.. 148842 records from Tasmanian Museum and Art Gallery provider for OZCAM. 14314 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 938 records from TTRS Mammals. 224 records from Donn?es du naturaliste DESCHATRE Thierry provenant de la base de donn?e du SINP ?le-de-France CETTIA. 6 records from Neotropical Chvalaea Papp & F?ldv?ri (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 6 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 587 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 4575 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 2 records from Benthic foraminifera abundance of Hole 42-376. 45 records from Brown bear monitoring data from Deosai National Park. 636 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 15 records from Feral Pigs - Sightings and Cull records - 2018-2019. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 7010 records from La familia Asclepiadaceae en M?xico. 46 records from Stable carbon and oxygen isotope record of Cretaceous planktonic foraminifera from DSDP (Table 1). 4 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 373 records from Otter survey of Ireland 2004 & 2005. 228 records from JOI - Herb?rio Joinvillea. 27 records from A revision of the African wolf spider genus Amblyothele Simon. 31 records from Occurrence of mammalia relicts at site Tokod-Nagyberek. 1 records from A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 6247 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 249 records from Donn?es opportunistes produites par Alexandre RUFFONI dans le cadre de l??laboration d?un guide de d?termination des larves de pl?copt?res. 81 records from Birdrace-Die_Ornithomaten-Herford. 4 records from First record of the millipede genus Nesorthomorpha Jeekel, 1980 in Vietnam with description of a new species (Diplopoda, Polydesmida, Paradoxosomatidae). 133152 records from Suivi Temporel des Rhopaloc?res de France (STERF). 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 15 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 1 records from A new genus and species of Apameini (Lepidoptera: Noctuidae) from Sichuan (China). 2360 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 103 records from Mammals (UWEP-MM). 84979 records from NINA Vanndata fisk. 411 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 1 records from A new species of Coleophora (Lepidoptera: Coleophoridae: Coleophorinae) from the Gal?pagos Islands, Ecuador. 510 records from Inventaires des cygnes du d?partement de l'Eure. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 38 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 602 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 25 records from Herpetofauna de la expedici?n Piedemonte Llanero - Proyecto Boyac? BIO UPTC. 96 records from Peces de la transici?n Andino-Amaz?nica del departamento del Caquet? - Proyecto Colombia BIO. 61 records from Alien Species in Poland - Plants. 323 records from Donn?es de VINCENT Alexis (SAPROX). 53062 records from British Antarctic Survey Argos satellite tracking data. 56 records from Donn?es de la structure For?ts en Aulnoye provenant de la base de donn?e du SINP ?le-de-France CETTIA. 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 230880 records from Soil bacterial diversity is associated with human population density in urban greenspaces. 3 records from Distribution of meiobenthos in sediment core M19_217-2 of the northeastern Atlantic (Table 1). 114 records from Total foraminifera counts of multinet M26/1_MSN844. 4 records from Microplankton abundance at bottle station SEPT-1999-K4. 7 records from Taiwanese deep-water chitons (Mollusca: Polyplacophora) and survey of chiton fauna of Taiwan. 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 165 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 383 records from Nannofossil abundance of Hole 66-490. 130 records from Synth?se de la R?partition des populations de bouquetin des alpes en 2005 (r?seau Ongul?s sauvages ONCFS-FNC-FDC). 3415 records from (Table 3) Occurrences of diatoms species in DSDP Hole 41-369A. 583 records from Donn?es du naturaliste Christian Desmier. 29646 records from (Table 2) Mollusc biostratigraphy of facies underlying the 'Braunkohlensande' in the Lauenburg district, north Germany. 9 records from New species of Glossoscolex and Fimoscolex earthworms (Oligochaeta: Glossoscolecidae) from Embrapa Forestry, Paran?, Brazil. 515 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 836 records from Odoanta of Akwa Ibom State University, Nigeria. 1197 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 270 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 192 records from Diversidad y conservaci?n del germoplasma de henequ?n Agave fourcroydes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 11884 records from Donn?es naturalistes de Franck NOEL. 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 1136 records from Nannofossil abundance of Hole 82-558A. 364 records from Natura 2000 ZPS Jarny - Mars-la-Tour. 446 records from Programme ACT : R?partition Etourneau sansonnet 2006 - 2010 Coordonn?es GPS Lambert 93. 3327 records from BioGIS - Mammals - SPNI. 2369 records from Chronicle of Nature - Phenology of Birds of Darwin Nature Biosphere Reserve. 90159 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Direcci?n General de Medio Natural y Pol?tica Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 13 records from Diatom abundance of Hole 60-460. 23 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 ?m. 18 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 ?m fraction. 216 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 5695 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 111 records from Review of Afrotropical Glenosema Kieffer (Hymenoptera, Bethylidae) with description of 13 new species. 154 records from Total foraminifera counts from multinet SO119_MSN1285. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 119353 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 13 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-104BX. 5934 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 176 records from Planktic foraminifera abundance of Hole 94-610B. 5883 records from MfN - Fossil vertebrates IV. 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 36737 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 1607 records from MEXU/Flora de Oaxaca. 70 records from (Table 4) Coiling direction changes of Neogloboquadrina acostaensis during the latest Miocene and early Pliocene of DSDP Hole 94-608 from the North Atlantic Ocean. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 6445 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 2082 records from Registros biol?gicos de flora para el desarrollo de acciones de evaluaci?n, seguimiento y monitoreo en los elementos priorizados de la estructura ecol?gica principal del distrito capital. Bogot? D.C.. 52 records from Occurrence of mammalia relicts at site Zigeunerfels. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 287 records from Nannofossil abundance of Hole 66-488. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 2 records from Description of lithologic section units of IODP Hole 325-M0052C. 97 records from Amphibiens filet/Marbotte-Ronval 2013. 47 records from Black Corals (Anthozoa: Antipatharia) from the Southwestern Atlantic. 3319 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crust?ceos, equinodermos y peces) del Santuario Islas e Islotes de Bah?a Chamela, Jalisco, M?xico. 7178 records from Ravensthorpe Range survey data. 56 records from Ictiofauna balseana y helmintos par?sitos asociados. 5 records from Scorpaena regina, a new scorpionfish (Teleostei: Scorpaenidae) from the east coast of Queensland, Australia. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 5 records from Schulinnenh?fe (Gelsenkirchen). 430 records from (Table 2) Some abiotic factors and distribution of benthic foraminifers in surface layer of bottom sediments from the littoral zone of the Kunashir Island (Pacific Ocean side). 2933 records from Donn?es naturalistes d'Alain BERLY. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 253 records from NZCS Upper Tapanahony Expedition 1991. 307 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 22 records from Tanzanian Vertebrate Collection. 32 records from Occurrence of mammalia relicts at site Bettelk?che. 33318 records from BrioCAT: Banco de datos de los bri?fitos de Catalu?a. 153 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/049-3. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 3 records from DD_cyano Targeted loci environmental. 347 records from Donn?es de la structure D?partement 78 provenant de la base de donn?e du SINP ?le-de-France CETTIA. 5823 records from (Table 3) Planktonic foraminifers from ODP Hole 114-704A. 1543 records from Abundance of algae in the Aral Sea. 29 records from Naturerfahrung. 60 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 205 records from Total foraminifera counts from M35/1_MSN1047. 937 records from Donn?es naturalistes de Damien Combrisson. 4142 records from Range table from benthic foraminifers in ODP Hole 159-962D. 6652 records from Inventory of plant species through Benin (West Africa). 19 records from Suivi des reptiles des landes du Technop?le du Madrillet. 150 records from Total foraminifera counts of multinet M12/3_MSN535. 553 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 4109 records from South Caribbean Diversity. 896 records from Data on agroforestry plant species of Benin. 4454 records from Insectes Hym?nopt?res Formicid?s de Corse. 29 records from Donn?es malacologiques du site Natura 2000 de Cessi?re-Montbavin. 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 2569 records from Radiolaria specimens from Korsfjorden Nov 1969 - May 1971. 873 records from Programme ACT : R?partition Grive musicienne 2006 - 2010 Coordonn?es GPS Lambert 93. 224 records from The Avian Collection of the Tana River Basin at the National Museums of Kenya's Ornithology Section.. 3458 records from Base de datos de la Sala de Colecciones Biol?gicas de la Universidad Cat?lica del Norte (SCBUCN). 19 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 5621 records from Plan d'Am?nagement participative de la For?t Class?e d'Al?djo (Togo). 1803 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 27 records from Benthic macrofauna abundance of sediment core 13078-013. 1127 records from Planktic foraminifera counts of sediment core RC14-35. 569 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 2 records from A new species of Aoruroides Travassos & Kloss, 1958 (Nematoda: Oxyuridomorpha Thelastomatidae) parasite of the wood-burrowing cockroach Panesthia angustipennis spadica (Shiraki, 1906) (Blattodea: Blaberidae: Panesthiinae) from Japan with comments on the validity of the genus Aoruroides. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 29 records from Taxonomic notes on Palearctic Podalonia Fernald, 1927 (Hymenoptera, Sphecidae), with descriptions of four new species. 1296 records from Avifauna de los Parques Ecol?gicos Distritales de Monta?a del Distrito Capital. 1699 records from Pollen record of sediment core Bokanjacko Blato 1. 21 records from New species and record of Nazeris Fauvel in southern China (Coleoptera, Staphylinidae, Paederinae). 661 records from Donn?es esp?ces Expertise IQE 311. 189 records from Microplankton abundance in the euphotic zone of the Aegean Sea in October-November 1991. 2550 records from Nematode genera abundance from Portuguese canyons HERMES HERMIONE. 155 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN734. 1 records from Tyrannosaurus rex from the McRae Formation (Lancian, Upper Cretaceous), Elephant Butte Resevoir, Sierra County, New Mexico. 21 records from (Tab. 2) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 1-4, Blake-Bahama Basin. 28214 records from India Biodiversity Portal publication grade dataset. 224 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 33 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 858 records from (Appendix 2) Diversity and foraminifera of sediment core M5/2_KL15. 3 records from New species of the spider genus Olios Walckenaer, 1837 (Araneae: Sparassidae: Sparassinae) from Laos. 257 records from Determinaci?n de la distribuci?n potencial de las especies nativas e introducidas de bamb? en M?xico.. 749850 records from Oiseaux de France m?tropolitaine en hiver 1977-1981. 4657 records from All herbarium specimens of grasses held at TAN herbarium. 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 704 records from Pollen counts of sediment core GeoB9503-5. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 ?m. 14 records from Nemertini - SMF. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 1 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 266 records from Chronicle of Nature - Phenology of Insects of Volzhsko-Kamsky National Nature Biosphere Rezerve. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_10-CTD121. 332 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 56 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 67 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 794 records from Macroarthropods, Narsarsuaq 2014, Greenland. 66620 records from Benthos monitoring in the intertidal mudflats of Pertuis-Charentais (Bay of Biscay) from 2004 on. 10774 records from Some Angiosperm Data of the Forest Herbarium Ibadan (FHI) Nigeria. 409 records from Records of fish species in coastal lagoons from Municipality of Arta, for the period 1999-2011. 1967 records from Fototrampeo de sistemas c?rsticos en el municipio de El Pe??n, Santander - Proyecto Colombia BIO. 32 records from Abundance of coccosphere-units of sediment core GIK23071-3. 200 records from Database_Dragonflies_ Madagascar Biodiversity Center PBZT. 2 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 44 records from Mam?feros peque?os en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 133 records from Nematode abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 817 records from Programme ACT : R?partition Tourterelle turque 1997 - 2001 Coordonn?es GPS Lambert 93. 4816 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 4 records from Dinoflagellate abundance of Hole 71-513A. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 234 records from Microzooplankton abundance measured on water bottle samples at station PS58/048-3. 243 records from Thistles species and abundance. 115 records from On the absence of the Green-tailed Trainbearer Lesbia nuna (Trochilidae) from Venezuela: an analysis based on environmental niche modelling. 222 records from Total foraminifera counts of multinet SO118_MSN1253. 6288 records from Macroinvertebrate abundance data from the littoral zone of a number of large New Zealand lakes. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 29559 records from Occurrences de vecteurs de maladies recens?es ? l'H?pital de M?nontin. 2111 records from Flora vascular acu?tica de la cuenca del R?o Tames?. 4 records from A new species of Pseudobunocephalus Friel, 2008 (Siluriformes: Aspredinidae) from the lower Tocantins and Mearim river drainages, North and Northeast of Brazil. 1278 records from Foraminifera abundance of Hole 45-396. 5664 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 4 records from A new species of Leptobrachella (Anura: Megophryidae) from southern Guangxi, China. 5 records from Two new nematode species of the genus Tobrilus Andr?ssy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 63 records from New contributions to the Eulophidae fauna from Morocco (Hymenoptera: Chalcidoidea) with comparison in the North African region. 1096 records from Donn?es naturalistes de St?phane ORIO. 702 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 155303 records from Base de datos de plantas vasculares del Pa?s Vasco: ARAN-EH. 382 records from Collection Echinodermata - ZMB. 260 records from Miljodir_naturtypekartlegging_2017. 244 records from WildesMoor bei Schwabstedt. 434 records from Inventario herpetofaun?stico del noroeste de Hidalgo. 406 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 677 records from The Paleontological Collections at the Bayerische Staatssammlung f?r Pal?ontologie und Geologie. 3 records from A new subspecies of Glabroculus elvira (Eversmann, 1854) (Lepidoptera, Lycaenidae) from the Dzhungarian Gobi desert, Mongolia. 7 records from Description of lithologic section units of IODP Hole 325-M0052A. 5 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR16. 212 records from Donn?es des naturalistes POHIER et LEFORT provenant de la base de donn?e du SINP ?le-de-France CETTIA. 7920 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 10 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 16387 records from CPAP - Herb?rio CPAP. 268 records from Bri?fitos del cerro Tacarcuna-Choc?, en el marco del proyecto Colombia BIO 2017. 190 records from CNMA/Colecci?n de Mam?feros de la Estaci?n de Biolog?a Chamela. 150 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 4 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 406 records from Harpactus Shuckard. 2968 records from Los crust?ceos dec?podos marinos: Actualizaci?n de la colecci?n carcinol?gica de la Facultad de Ciencias Biol?gicas, UANL. 2189 records from Jard?n Bot?nico Atl?ntico, Gij?n: JBAG. 26 records from Microzooplankton abundance and biomass at station TT045_26-3. 51 records from Donn?es du naturaliste MARCHAL Olivier provenant de la base de donn?e du SINP ?le-de-France CETTIA. 164133 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 1442 records from Cowan Tetrapod Collection - Herpetology. 173 records from Total foraminifera counts from multinet M31/3_MSN898. 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 232 records from Phytoplankton abundance at station CD46_0705C#4. 1 records from Eudorylaimus kahaqensis sp. n. (Nematoda: Dorylaimida: Qudsianematidae), an interesting new species from Iran. 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 13 records from Donn?es additionnelles d'Echasse blanche Himantopus himantopus 1980-1991 nicheuse probable ou certaine (hors p?riode atlas 1985-1989). 84 records from Shellfish (MNHM-MS). 29 records from Hemmerder Schelk (Unna). 2 records from The harvestman genus Taracus Simon 1879, and the new genus Oskoron (Opiliones: Ischyropsalidoidea: Taracidae). 5 records from New taxa and notes on crickets of the subfamily Landrevinae (Orthoptera: Gryllidae) from Brunei Darussalam, Borneo. 2 records from Annotated checklist of the false blister beetles (Coleoptera: Tenebrionoidea: Oedemeridae) from Iran. 53 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 237 records from Avifauna asociada a humedales urbanos del municipio de Quibd? - Choc?, 2019. 3 records from Description of a new species of Music frogs (Anura, Ranidae, Nidirana) from Mt Dayao, southern China. 3 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 16 records from jamaica_invasive_alien_species. 120 records from Naturschutzgebiet Lochbusch-K?nigswiesen. 15 records from Integrative taxonomy reveals cryptic diversity in neotropical grasshoppers: taxonomy, phylogenetics, and evolution of the genus Sphenarium Charpentier, 1842 (Orthoptera: Pyrgomorphidae). 19 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 1 records from A new tardigrade species of the genus Neostygarctus Grimaldi de Zio et al., 1982 (Tardigrada, Arthrotardigrada) from the Great Meteor Seamount, Northeast Atlantic. 86 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 6782 records from Odonata de Veracruz. 2 records from First record of Cephenniini on Christmas Island, with updated checklist of world Cephennomicrus species and summary of their distribution (Coleoptera, Staphylinidae, Scydmaeninae). 150 records from Schulgarten Huttenheim (Philippsburg/Baden). 441 records from L?nea base del medio bi?tico en los bosques dentro de la zona propuesta para Acuerdos de Conservaci?n Voluntaria en la microcuenca de la Quebrada Aguazula - Rinc?n del Soldado_Yopal. 1319 records from Inventaire et suivi Avifaune. 934 records from Botanic Garden of the Finnish Museum of Natural History. 89 records from Planktic foraminifera abundance of Hole 63-470A. 7653 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 60 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2247-1. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 15 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1024. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 20 records from B?squeda de poblaciones de la liebre end?mica Lepus flavigularis. 1596 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases ? Wolf, (Canis lupus) Wild Boar (Sus scrofa) and Roe Deer (Capreolus capreolus) [camera-trapping] - [2011-2014]. 5 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 255 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 10295 records from Donn?es naturalistes d'Olivier GARGOMINY saisies sous cardObs. 286 records from Inventory of the Heteroptera (Insecta: Hemiptera) in Komaba Campus of the University of Tokyo, a highly urbanized area in Japan. 14 records from New species of Australian microgastrine parasitoid wasps (Hymenoptera: Braconidae: Microgastrinae) documented through the ? Bush Blitz? surveys of national reserves. 626 records from Estado actual de conservaci?n de liebres y conejos en categor?a de riesgo en M?xico. 1249 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 16506 records from Database for alien invasive plants occurrences in Germany. 66 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 1333 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 884 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 533 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 80 records from Foraminifera distribution of sediment core SDSE189. 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapaj?s basin, Brazil. 51 records from New species and new records of terrestrial isopods (Crustacea, Isopoda, Oniscidea) of the families Philosciidae and Scleropactidae from Brazilian caves. 3673 records from Spider (NSMK-SP). 156 records from The ceratioid anglerfishes (Lophiiformes: Ceratioidei) of New Zealand. 4125 records from OUPR - Herb?rio "Professor Jos? Badini". 2017 records from Flore des reliques foresti?res de la commune de Dangbo. 15 records from Nannofossil abundance of Hole 58-442B. 3 records from Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae). 17 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 334 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 12399 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San crist?bal). 74 records from Chronicle of Nature - Phenology of Mushrooms of Baikalsky State Nature Biosphere Reserve. 27 records from Planktic foraminifera abundance of Hole 18-174. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 2693 records from California State University, Long Beach Mammals. 540 records from (Appendix 3) Abundances of benthic forminifera in DSDP Hole 74-525A. 234 records from Royal Saskatchewan Museum - Ichthyology Collection. 981 records from Monitoreo de la ocupaci?n del Oso Andino Tremarctos ornatus en el Parque Nacional Natural Chingaza 2010. 5069 records from Donn?es mammif?res Midi-Pyr?n?es enregistr?es dans BazNat - Lot 2. 92 records from Nottekanal, Klasse 7 - 10. 597 records from Percentages of planktonic foraminifera species in sediment core V30-40. 29 records from A review of the Cyana bianca (Walker, 1856) species-group with descriptions of a new species and a new subspecies from Indochina (Lepidoptera, Erebidae, Arctiinae). 810 records from Environmental long read amplicons of soil fungi across Podzol soil profile. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 2 records from A revision of the Australian species of the genus Melobasis Laporte & Gory 1837 (Coleoptera: Buprestidae), Part 2 (Revision of the nervosa species group). 4733 records from Inventaire des Mollusques Sphaeriidae de France. 742 records from Programme ACT : R?partition Alouette des champs 2000 - 2004 Coordonn?es GPS Lambert 93. 16885 records from donn?es aran?ologiques de CORNIC Jean-Fran?ois. 8 records from Four new and three newly recorded species of Diduga Moore, [1887] (Lepidoptera Erebidae, Arctiinae) from China. 54 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 3687 records from Clare Biological Records Centre Dataset 2004-2007. 3030 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 2 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 4 records from A new glass sponge genus (Hexactinellida: Euplectellidae) from abyssal depth of the Yap Trench, northwestern Pacific Ocean. 25765 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 3919 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 2 records from Two new species of the genus Crangonyx Bate, 1859 (Amphipoda: Crangonyctidae) from the St. Marks River Basin with notes on the ? Crangonyx floridanus complex ?. 174 records from Nematode abundances in sediments from the H?kon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas?. 3 records from The genera Agelosus Sharp, 1889 and Apecholinus Bernhauer, 1933 in Taiwan (Coleoptera: Staphylinidae: Staphylinini: Staphylinina). 20 records from Truchas Mexicanas. 50 records from Flora und Fauna im Brexbachtal. 13639 records from Senckenberg - CeDAMar Resource. 51 records from Marine metagenome ICM_VAG. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14619 records from Ontario Breeding Bird Atlas 1981-1985. 6927 records from Estudios bi?ticos (Plantas, Fauna Ed?fica, Anfibios y Aves) en los Complejos de p?ramos las Hermosas y Chil?-Barrag?n.. 3399 records from Colecci?n de Mam?feros del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from On the taxonomy of Lygosoma bampfyldei Bartlett, 1895 (Squamata: Scincidae) with descriptions of new species from Borneo and Peninsular Malaysia and the resurrection of Lygosoma schneideri Werner, 1900. 391 records from Vegetaci?n de sistemas c?rsticos en el municipio de El Pe??n, Santander - Proyecto Colombia BIO. 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 91 records from Donn?es de la naturaliste Marie Melun. 1419 records from Diversity of algae in wetlands. 358 records from Donn?es rhopaloc?res collect?es par le CEN Aquitaine entre 1970 et 2015. 2 records from A new species of freshwater crab of the genus Strengeriana Pretzmann, 1971, from El Jard?n Natural Reserve, Quind?o, Colombia (Crustacea: Decapoda: Pseudothelphusidae). 349 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 1 records from Integrative description of Macrobiotus canaricus sp. nov. with notes on M. recens (Eutardigrada: Macrobiotidae). 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 72 records from Donn?es sur les Opisthobranches et Planaires de Mayotte. 3 records from Microplankton counts and carbon biomass at station TT011_3-CTD33. 381 records from Estudio taxon?mico de moluscos terrestres y dulceacu?colas de la regi?n maya de M?xico I. Reserva de la Biosfera Pantanos de Centla. 4 records from Open-holed trapdoor spiders of the genus Teyl (Mygalomorphae: Nemesiidae Anamini) from Western Australia?s Pilbara bioregion: a new species and expanded phylogenetic assessment. 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 129 records from Planktic foraminifera abundance of Hole 94-611. 3 records from Abundance of zooplankton in the Aral Sea. 11193 records from Baselines Initiative 16S rRNA gene dataset: Baselines Amplicon Release 1 (R1) Caribbean Sea near Curacao (including saline pond samples in Curacao) 2015. 3050 records from Distribution of dead benthic foraminifera in surface sediments of the Norwegian Sea (Table 3). 9 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 6 records from Two new species of the spider genus Wanniyala Huber & Benjamin, 2005 (Araneae Pholcidae) from Sri Lanka. 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 1752 records from Phytoplankton abundance in surface water during cruise CD61. 3 records from Discovery of a new species of Lacon Laporte (Coleoptera: Elateridae: Agrypninae) endemic to Cyprus, with a modified tarsal morphology. 29 records from Total foraminifera counts of trap L3_92_45. 88 records from "Schlechteberg" Ebersbach/Sa.. 8017 records from Colecci?n de Herpetolog?a del Instituto de Ciencias Naturales (ICN-MHN-Her). 751 records from Programme ACT : R?partition Pie bavarde 2007 - 2011 Coordonn?es GPS Lambert 93. 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 4686 records from (Table 1) Occurrence of selected planktonic foraminifers, other microfossils, and lithologic components at DSDP Hole 96-619. 2 records from Three new species of Synagelides Strand, 1906 from China (Araneae: Salticidae). 124922 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 136 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1371. 52 records from Nannofossil abundance of Hole 1-3. 1 records from A new species of Metatanais Shiino, 1952 (Crustacea, Tanaidacea, Paratanaoidea) from Australian coral reefs, with a redefinition of the genus. 641 records from Planktic foraminifera counts of sediment core V29-64. 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 191 records from sediment microorganism Metagenome. 10 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 696 records from Staatliches Museum f?r Naturkunde Stuttgart, Herbarium. 1 records from A new Myxobolus (Cnidaria: Myxosporea) infecting the ornamental catfish Corydoras schwartzi from the Purus River in Brazil. 135 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - Birdrace-Pody&Co.-Pl?n. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Cear? State) and Sete Cidades (Piau? State) National Parks, Northeastern Brazil. 11616 records from (Appendix II) Planktonic foraminiferal biostratigraphy of ODP Site 113-690. 2427 records from Base de datos y colecci?n de distintos grupos del zooplancton de regiones marinas prioritarias de Jalisco y Colima en el Pac?fico mexicano (Larvas de peces). 251 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 1962 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 2 records from A new deep-sea Cirripedia of the genus Heteralepas from the northeastern Atlantic. 244 records from Phytoplankton abundance during Arne Tiselius cruise AT91/2. 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 1101 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 403 records from Revision of Chondrocyclus s. l. (Mollusca: Cyclophoridae), with description of a new genus and twelve new species. 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 55 records from SNH Invertebrate Site Condition Monitoring 2015: Rinns of Islay SSSI. 464 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 18 records from "Biodiversidad en el valle de Cuatro Ci?negas". (?caros acu?ticos). 17 records from Peces de la expedici?n en el p?ramo El Consuelo, Boyac? - Proyecto Boyac? BIO. 110 records from Phytoplankton abundance at station Rigel_3_2005-07 in July 2005, Chipana, Chile. 139730 records from Atlantic Reference Centre Museum of Canadian Atlantic Organisms - Invertebrates and Fishes Data. 3428 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 2 records from Lemyra persephone, a new autumnal species from Yunnan, southwestern China (Lepidoptera, Erebidae, Arctiinae). 724565 records from Finnish Floristic Database (Literature Sources). 180 records from (Table 7) Distribution of the large, many-chambered Globigerinelloides species in DSDP Hole 79-545. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 72176 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 1773 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 32313 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 633 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 4534 records from Amphibian specimens. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 232 records from Inventaire avifaune. 2 records from A new Paramathes Boursin, 1954 (Lepidoptera, Noctuidae) species from China. 15922845 records from iNaturalist Research-grade Observations. 37 records from Content of coarse fraction and G. menardii in sediment corev V16-202. 143 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 125 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 2584 records from Range table from benthic foraminifers in ODP Hole 154-929A. 1 records from New articulated asteroids (Echinodermata, Asteroidea) and ophiuroids (Echinodermata, Ophiuroidea) from the Late Jurassic (Volgian / Tithonian) of central Spitsbergen. 15 records from Sphyraena stellata, anew barracudafromthe Indo-Pacific, with redescriptionsofS. helleri Jenkins, 1901 and S. novaehollandiae G?nther, 1860 (Perciformes: Sphyraenidae). 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 670 records from Project for Reef Fish Monitoring. 5205 records from FBIP:IZIKO-UCT:Historical Survey (1930-1980). 76 records from An update on the spider genus Hexophthalma (Araneae: Sicariidae) in the Afrotropical region, with descriptions of new species. 553 records from Composici?n flor?stica y estructura de una parcela permanente en bosques humedos tropicales del resguardo Ember? Chontadural, municipio de Mutat?, Antioquia. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 4200 records from Inventaire de la flore des ENS des Pyr?n?es-Atlantiques 2011-2012. 2 records from Donn?es de L?pidopt?res de Bruno DAUGET - D?pt des PYRENEES-ORIENTALES (66). 35 records from Macrohongos en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 88632 records from Hymenoptera collection of the Finnish Museum of Natural History. 912 records from JOIw - Xiloteca Joinvillea. 41 records from Planktic foraminifera counts of sediment core V28-128. 4 records from Olbiogaster Osten Sacken (Diptera: Anisopodidae) from Mexico, with the description of three new species. 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 16 records from (Table 4b) Abundances of Globorotalia menardii in sediment core INMD-113BX. 4 records from Black grouse lek survey in Wester Ross and Skye 2009. 490 records from Sequences obtained from two sponge genera (Hyrtios, Aiolochroia), one zoanthid (Palythoa), and marine sediments. Metagenome. 155 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 179 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 120 records from Flora pol?nica de las llanuras de Sonora, al sur de Hermosillo. 565 records from Planktic foraminifera abundance of Hole 49-407. 54 records from VFD-H: MIttelgebirgsweide. 339 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE218. 105 records from Microzooplankton abundance measured on water bottle samples at station PS65/587-1. 187 records from Nannofossil abundance of Hole 7-62A. 3224 records from Amphibiens de Guyane. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 9 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 18 records from Nannofossil abundance of Hole 9-82. 1186 records from Nannofossil abundance of Hole 75-530A. 24 records from Planktic foraminifera abundance of Hole 20-200A. 2 records from Two new species, including one representing a new genus, of the West African millipede family Campodesmidae (Diplopoda: Polydesmida). 4356 records from (Table 18) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-593. 60 records from Smear slide analysis on sediment core GeoB4206-1. 4 records from Collection Myriapoda - SNSD. 49540 records from Dreal Corse - Base Ogreva. 1857 records from Censo de aves acu?ticas nidificantes de la Comunidad Aut?noma del Pa?s Vasco. 78605 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 1357 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 1954 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 25 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 6 records from Sarcodine counts and carbon biomass at station TT011_10-CTD123. 3546 records from Dorset SW Pilot species dataset. 1231 records from Mammal Collection (Vouchers [Standard Sampling at Pathogen Plots]). 669 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 222 records from Revision of the family Chasmocarcinidae Ser?ne, 1964 (Crustacea, Brachyura, Goneplacoidea). 6080 records from Sepsidae (Diptera) records from Britain and Ireland to 1985. 9 records from UTEP Fish (Arctos). 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 5 records from A review of Gonothrombium Feider, 1950 (Actinotrichida: Microtrombidiidae) with description of a new species from Turkey. 93662 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 79 records from Etude d'?tat initial de la biodiversit? dans le cadre des EIES sur les plateaux situ?s dans la zone sud (Pompo) de la concession mini?re de Guinea Alumina Corporation(GAC) dans la region de Bok? (CESP2016-022). 138 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 1 records from A new species of Anthiadinae (Teleostei: Serranidae) from S?o Pedro and S?o Paulo Archipelago, Brazil, Equatorial Atlantic.. 1 records from Occurrence of mammalia relicts at site High Furlong. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 36 records from University of Sindh Jamshoro Herbarium. 2924 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-K?stner-Schule erforscht das Bachemer Wiesental. 85 records from Ecolog?a de comunidades microbianas en las aguas subterr?neas de Cuatroci?negas, Coahuila. 3 records from A new group of species within the bee genus Ruizantheda, with a revised key to the males of the genus (Hymenoptera: Halictidae: Caenohalictini). 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 20891 records from Brachycera (Diptera) records from Britain and Ireland to 1990. 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 26 records from Bulletin de la Soci?t? Linn?enne de Bordeaux, Tome 145 (N.S) n? 38 (1), 2010 - Donn?es faune. 14 records from Benthic foraminifera abundance of Hole 96-620. 86616 records from Marine Offshore Seabed Survey data held by JNCC. 3566 records from FrogWatch SA. 105 records from Nanoplankton abundance at station GeoB2006-4. 75 records from Donn?es naturalistes de Fran?oise SERRE-COLLET. 374 records from (App 5) Relative contents of benthic foraminifera species in Holocene sediments from Core BP01-62/04. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 319 records from Donn?es naturalistes de Monsieur LEFEBVRE Fran?ois. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 2331 records from Range table from planktonic foraminifers in ODP Hole 144-872C. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 96508 records from Herbarium of Taiwan Forestry Research Institute. 90 records from Swedish Malaise Trap Project (SMTP) - Pallopteridae. 11 records from ALP-PAGES_2017_12_18. 23 records from Ackerrain Pl?nhagen. 6936 records from Colecci?n Herpetol?gica (Anfibios) del Museo de Historia Natural de la Universidad Industrial de Santander. 242 records from Malawi-Histeridae-Biodiversity-Data. 1004 records from Donn?es odonates. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 1994 records from Actualizaci?n de la base de datos de la Colecci?n Regional Durango (Mammalia) (Tejido). 1447 records from Planktic foraminifera abundance of Hole 7-64. 25 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 1 records from Museu Paraense Em?lio Goeldi - Acanthocephala Collection. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 22 records from Bachabschnitt der Nette (Osnabr?ck). 371 records from Species occurring in the mytilid and alvinellid communities within the 9?N hydrothermal field at the East Pacific Rise. 2 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 712 records from Programme ACT : R?partition Alouette des champs 2010 - 2014 Coordonn?es GPS Lambert 93. 6 records from Ontogeny as an important part of integrative taxonomy in tergipedid aeolidaceans (Gastropoda: Nudibranchia) with a description of a new genus and species from the Barents Sea. 49 records from Ejemplares de Criptogamas de Chile en el Herbario CORD. 214 records from Total foraminifera counts of multinet M21/1_MSN608. 17295 records from The cryptogamy collection (PC) at the Herbarium of the Mus?um national d'Histoire Naturelle (MNHN - Paris). 11664 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 5855 records from Actualizaci?n y depuraci?n de las bases de datos de la Colecci?n Nacional de Helmintos: P085 y Q028. 4038 records from Consolidaci?n de la colecci?n de referencia de peces de la Estaci?n Mazatl?n, (ICMyL-UNAM) e implementaci?n de los mecanismos para su manejo y consulta. 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 1297 records from Recensement et distribution Mammif?res marins Guadeloupe Antilles fran?aises (AET). 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 8 records from Taxonomy of Litoria graminea (Anura: Hylidae), with descriptions of two closely related new species. 272 records from Inventaire malacologique des murs restaur?s en pierre s?che en lien avec l'association "une pierre sur l'autre". 1 records from Dinoflagellate abundance of Hole 38-343. 78 records from Banco de Semillas de Boyac?. 1 records from Dolichocephala Macquart of Thailand (Diptera: Empididae: Clinocerinae). 120071 records from CAS Botany (BOT). 2225 records from Donn?es naturalistes d'Ana?s MAS. 1 records from A new genus of Oxypodina from Kyrgyzstan (Coleoptera, Staphylinidae, Aleocharinae, Oxypodini). 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 1057 records from Palynological analysis of sediment core GeoB9508-5. 70 records from Plasm bearing foraminifera counts from M35/1_MSN1059. 8 records from The Myriapoda & Onychophora collection (MY) of the Mus?um national d'Histoire naturelle (MNHN - Paris). 65 records from Donn?es du/de la naturaliste Thibault Marie Th?r?se provenant de la base de donn?e du SINP ?le-de-France CETTIA. 2291 records from (Table 3) Distribution of benthic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 508 records from Barents Sea Zooplankton ? March and May 1998 and July 1999. Zooplankton sampling on board the Norwegian R/V Jan Mayen, program ALV. 6 records from Abundance of benthos infauna at station GIK23065-1. 27254 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 214 records from Range table from benthic foraminifers in ODP Hole 198-1207B. 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 593 records from Flux data of NU2_trap (Table A1). 4 records from Planktic foraminifera abundance of Hole 17-166. 2712064 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 178 records from (Fig. 3) Relative abundance of Neogloboquadrina pachyderma (s) in sediment core MD99-2343. 830 records from Soil DNA extracted from Robinson Ridge, East Antarctica Raw sequence reads. 228 records from Bishop's University Insect Collection (BUIC). 5 records from Two new species of Brueelia K?ler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 18 records from ALTERECO_2017_12_18. 29 records from Caracterizaci?n Ecol?gica de la Fauna del P?ramo de Frontino o del Sol. 6949 records from MBON POLE TO POLE: SANDY BEACH BIODIVERSITY OF YUCATAN COAST. 5346 records from Sediment metagenome. 3 records from New species of Prolachesilla Mockford & Sullivan (Psocodea: ? Psocoptera?: Lachesillidae: Graphocaeciliini) from Bolivia and Mexico. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 15255 records from Anymals+plants - Citizen Science Data. 43056 records from Tartu University fossil collections. 4 records from Two new species of Nealiolus Mason (Hymenoptera, Braconidae, Brachistinae) reared from pest weevils (Coleoptera, Curculionidae). 2 records from Description of a new subspecies of Prosopocoilus antilopus (Swederus, 1787) (Coleoptera: Lucanidae) from Annob?n Island, Gulf of Guinea. 22 records from Fifteen new species and a new country record of Labomimus Sharp from China, with a checklist of world species (Coleoptera: Staphylinidae: Pselaphinae). 2 records from First record of the genus Phanoperla Banks, 1938 (Plecoptera: Perlidae) from mainland China, with description of a new species. 5156 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 3756 records from UMNH Reptiles and Amphibians Collection (Arctos). 1571 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 849 records from CNAN/Scorpiones. 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 490 records from Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 165 records from Mortensen Th. And Steuer Ad. 1937. The fishery grounds near Alexandria. XIII Echinoderma. Notes and Memoirs No 21. Hydrobiology and Fisheries Directorate, Egypt. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 54535 records from The fishes collection (IC) of the Mus?um national d'Histoire naturelle (MNHN - Paris). 462 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 6 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 114 records from BIRDRACE Di-Bi-Di-Birder. 492 records from Range table from planktonic foraminifers in ODP Hole 155-930C. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 6 records from A new species of the genus Liljeborgia Spence Bate, 1862 (Crustacea: Amphipoda: Liljeborgiidae) associated with the burrows of the spoon worm Urechis unicinctus in the Sea of Japan. 9811 records from Colecci?n, preservaci?n y caracterizaci?n de cultivares criollos de origen espa?ol de trigo y centeno de M?xico. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 19665 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 424 records from Collection de C.C.H. Jongkind aux Monts Nimba. 2 records from Museo Provincial de Ciencias Naturales ?Florentino Ameghino?, Santa Fe, Argentina - Colecci?n Aves Nidos (MFA-ZV-Or-N). 63 records from Donn?es du/de la naturaliste Champagne Alain provenant de la base de donn?e du SINP ?le-de-France CETTIA. 2 records from Argia mauffrayi n. sp. from Ecuador (Odonata: Coenagrionidae). 27841 records from Amphibian Specimens. 66 records from Rhopalocera of Martinique. 20 records from Benthic macrofauna abundance of sediment core 13077-087. 1914 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 394 records from ?tude de l?pidopt?rologie compar?e. 48769 records from Flora of the Sto?owe Mts.. 3 records from A redescription and a synonym in the South Asian millipede genus Xenobolus Carl, 1919 (Spirobolida, Pachybolidae). 7807 records from Occurrence data of dragonflies available at the National Museums of Kenya's Natural History Collection, Invertebrates Zoology Section.. 333 records from Macroinvertebrados acu?ticos asociados a humedales urbanos del municipio de Quibd? - Choc?, 2019. 100 records from (Table 5) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the Lesches en Diois section. 84 records from BIRDRACE Bielefinken. 1660 records from Synth?se de la R?partition des populations de cerf ?laphe en 1985 (r?seau Ongul?s sauvages ONCFS-FNC-FDC). 4 records from Unraveling the species diversity and relationships in the Leptodactylus mystaceus complex (Anura: Leptodactylidae), with the description of three new Brazilian species. 2112 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 44 records from Phytoplankton abundance in surface water in 1997, Ancon, Peru. 1 records from Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini. 35 records from Inventaire et suivi de la faune ?cras?e. 18 records from Microzooplankton abundance and biomass at station TT043_7-20. 1000 records from nsmk_mm_2019. 47 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 33 records from Chronicle of Nature - Phenology of Arachnids of Visimsky Nature Biosphere Reserve. 112 records from Caracterizaci?n de Flora de la Reserva Forestal Protectora Regional Brisas del Rinc?n. 687 records from gas hydrate bearing sediment Raw sequence reads. 71 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 371 records from Benthic foraminifera and algae abundance of Hole 81-554A. 111 records from Donn?es esp?ces - Expertise IPE 15. 13 records from A new Ovia species (Araneae, Lycosidae) from Singapore, with the transfer of Pardosa alboannulata Yin et al., 1997. 1056 records from Diatom assamblage in samples from sediment trap OG4. 3 records from Seven new species of the cicada genus Guyalna Boulard & Martinelli, 1996 (Hemiptera: Cicadidae: Fidicinini) with a re-description of the type species. 4 records from Distribution of meiobenthos in sediment core M23_149 of the northeastern Atlantic (Table 1). 28 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 455 records from Range table from planktonic foraminifers in ODP Hole 180-1118A. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 376 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 1 records from Studies in Australian Tettigoniidae: New Fully-winged Agraeciini From Northeastern Australia (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini). 170524 records from England Non Native Species records 1965 to 2017. 217 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 1 records from A new macropterous genus with a new species of Vianaididae (Heteroptera, Tingoidea, Vianaididae) from Peru. 161 records from Swedish Malaise Trap Project (SMTP) - Rogadinae. 1045 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-175-1. 7 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 42 records from (Appendix 7) Abundance of Neogloboquadrina pachyderma in sediment core MD01-2444. 4 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 3350 records from Reef Check in Taiwan ???????. 1 records from Microplankton counts and carbon biomass at station TT011_12-CTD150. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 836 records from Colecci?n Ornitol?gica de la Universidad Tecnol?gica del Choc?. 1 records from New morphological information on Simulium wygodzinskyorum Coscar?n & Py-Daniel, 1989 (Diptera: Simuliidae). 909 records from The Azooxanthellate Scleractinia (Coelenterata: Anthozoa) of Australia. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 145 records from Gronau - auf der Suche nach dem Neunauge. 95 records from Conocimiento de la diversidad y distribuci?n actual del ma?z nativo y sus parientes silvestres en M?xico (Tamaulipas). 1120 records from Programme national de science participative sur la Biodiversit? Littorale (BioLit). 9 records from Distribution of meiobenthos in sediment core M19_197-2 of the northeastern Atlantic (Table 1). 1 records from Discovery of the transantarctic distribution of the genus Metanteon Olmi (Hymenoptera: Dryinidae), with description of a new species from New Caledonia. 1393 records from Lepidoptera from Rancho Grande, Rond?nia, Brasil. 9083 records from Inventaire de la flore des Pyr?n?es-Atlantiques 2007-2008 - Littoral. 1482 records from Nannofossil abundance of Hole 94-607. 2081 records from Thrips (Thysanoptera) in Norway. 9391 records from Levantamento de Mam?feros do Parque Nacional da Qui?ama - INBAC/RWCP - 2017. 227 records from Range table from planktonic foraminifers in ODP Hole 159-961A. 58480 records from AUM Fish Collection. 69 records from Entdeckertour am Muldestausee 1/05. 88576 records from University of Colorado Museum of Natural History Herbarium Vascular Plant Collection. 613 records from Implementaci?n de la bioindicaci?n en el R?o Cauca - 2016. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 104 records from BID-Malawi-Arctiidae-Biodiversity-Data. 43 records from Antarctic and sub-Antarctic Lophogastrida occurrences. 53 records from Plasm bearing foraminifera counts of multinet M21/5_MSN740. 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulid?es d'Europe. 4 records from New species of Rhizomyces (Ascomycota, Laboulbeniales) parasitic on African stalk-eyed flies (Diptera, Diopsidae). 2 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 122 records from BIOTOPE_2017_12_18. 125449 records from BioGIS - Vascular plants - A. Danin's grid database. 411 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 5420 records from Colec??o Entomol?gica do Museu de Hist?ria Natural de Maputo. 3 records from Revisiting Calohypsibiidae and Microhypsibiidae: Fractonotus Pilato, 1998 and its phylogenetic position within Isohypsibiidae (Eutardigrada: Parachela). 5011 records from Inventario arb?reo del Jard?n Bot?nico Universitario del campus Mel?ndez de la Universidad del Valle, Santiago de Cali.. 241 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 724 records from Heritage Trees of Ireland. 613 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 42 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 792 records from Nannofossil abundance of Hole 40-362. 5534 records from Variation in freshwater stream sediment community 16S rRNA profiles along an urbanization gradient. 73 records from VFD-HH/SH: Pferdweide Lammert. 2140 records from Donn?es esp?ces - Expertise IQE 92. 34 records from The interstitial subsoil fauna of the upper beach level at Sarso Beach, Red Sea (Table 2). 748 records from Planktic foraminifera counts of sediment core V14-81. 182 records from Collection Polychaeta - ZSRO. 140 records from Donn?es du/de la naturaliste LUPOLI ROLAND provenant de la base de donn?e du SINP ?le-de-France CETTIA. 16774 records from imr_mareano_rpsledge. 26 records from Nannofossil abundance of Hole 3-14. 96 records from Elaboraci?n de la base de datos de la colecci?n de cepas de bacterias fitopat?genas de la Direcci?n General de Sanidad Vegetal. 2 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 182 records from Nannofossil abundance of Hole 55-433. 8 records from RISC Non-Native Species Records for Zebra Mussel. 37 records from Planktic foraminifera abundance of Hole 73-522A. 844 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 113223 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 8 records from Systematics, host plants, and life histories of three new Phyllocnistis species from the central highlands of Costa Rica (Lepidoptera, Gracillariidae, Phyllocnistinae). 39 records from Phytoplankton abundance at station Rigel_2_2005-03 in March 2005, Chipana, Chile. 675 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A. 9299 records from Sawfly (Symphyta) records from iRecord. 5759 records from Donn?es de la structure CERF (Centre d'Etude de Rambouillet et de sa For?t) provenant de la base de donn?e du SINP ?le-de-France CETTIA. 4 records from Description of the males of Lincus singularis and Lincus incisus (Hemiptera: Pentatomidae: Discocephalinae). 92 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 37 records from Occurrence of mammalia relicts at site G?nnersdorf. 67 records from Relative abundance of coccolith species in surface sediment samples from the Mid-Atlantic Ridge. 180 records from Freshwater fish records via iRecord - additional species. 23 records from Abundance of benthos infauna at station GIK23055-1. 2295 records from Invasive species - Fallopia japonica on river dikes along the river Zeeschelde, Rupel and Durme. 1 records from Description of a new whitefly? Pealius satakshiae Dubey (Hemiptera: Aleyrodidae) ? infesting Quercus leucotrichophora (Fagaceae) in the Western Himalaya? India. 1 records from New species of Dugdaleiella, gen. nov., Kozloviella, gen. nov., and Pfitzneriella Viette from upper elevation Andes of Ecuador and Peru (Lepidoptera: Hepialidae). 22 records from Planktic foraminifera of sediment core GeoB1407-2. 13 records from Benthic macrofauna abundance of sediment core 13200-017. 5 records from Lichen diversity in colombian caribbean dry forest remnants. 4198 records from Planktic foraminifera (%) of sediment core MD96-2085. 1 records from A new species of Otothyropsis (Siluriformes: Loricariidae) from the upper R?o Paran? basin, Paraguay, with a discussion of the limits between Otothyropsis and Hisonotus. 155 records from Abundance of radiolaria at station LV28-42-1. 4391 records from (Table 2) Calcareous nannofossil abundance in ODP Hole 164-994C sediments. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 4 records from Sponges of the family Esperiopsidae (Demospongiae, Poecilosclerida) from Northwest Africa, with the descriptions of four new species. 91 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 ?m fraction. 203 records from Nannofossil abundance of Hole 67-496. 566 records from Relative abundance of benthic foraminifera in sediment core SO90-137KA. 852 records from Observatoire des Mammif?res marins de l'Archipel Guadeloup?en. Suivi Dauphins Les Saintes. 569 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 841 records from Database on reference specimens for medicinal plants of the Rubiaceae family, conserved at the CNARP herbarium. 2 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 2 records from A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae). 525 records from Flora y fauna asociada al h?bitat del Manat? antillano en la Ci?naga de Paredes, Magdalena Medio Santandereano. 361 records from Colecci?n de Crust?ceos del Instituto de Ciencias Naturales (ICN-MHN-Cr). 3006 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 17 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 235 records from Pollen and spore abundance of Hole 42-381. 9 records from On the Neotropical spider genus Tullgrenella Mello-Leit?o, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 324902 records from Estonian Nature Observations Database. 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 398 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Site 115-711. 38375 records from Botanical Museum, Copenhagen, Mycology Herbarium. 1599 records from Inventaire des bois par esp?ce v?g?tale de la for?t class?e de Ziama en Guin?e Foresti?re (BID-AF2015-0066-REG). 7 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 268052 records from Biodiversit?tsdatenbank des Landes Salzburg. 1095 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 11305 records from NCSM Mammals Collection. 17 records from Nannofossil abundance of Hole 52-418. 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 24 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 103 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 11 records from Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae). 235 records from Chronicle of Nature - Phenology of Insects of Kaniv Nature Reserve. 770 records from Niv? Bay species list, Zealand, Denmark. 3317 records from Estudio taxon?mico y zoogeogr?fico de ?reas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, M?xico. 171 records from Fungal Bioblitz in Bia?owie?a Primeval Forest at 18th Congress of European Mycologists. 7 records from Swedish Malaise Trap Project (SMTP) - Mymar. 855 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 770 records from Nannofossil abundance of Hole 64-476. 7255 records from Colecci?n general del plantas vasculares del Herbario JBB. 3118 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 45 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 91645 records from Colecci?n de Entomolog?a del Instituto de Investigaci?n de Recursos Biol?gicos Alexander von Humboldt (IAvH-E). 7 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-089. 272720 records from Parc_National_de_Port_Cros_2017_12_18. 38400 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 15 records from Morphology and molecular data reveal the presence of two new species under Rhamdia quelen (Quoy & Gaimard, 1824) (Siluriformes: Heptapteridae) species complex. 1 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 30 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 488 records from Planktic foraminifera distribution of sediment core SU81-07. 926 records from Determinaci?n del estado actual de cinco especies de cact?ceas amenazadas del estado de Tamaulipas, M?xico. 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 277 records from Aunar esfuerzos y recursos t?cnicos, econ?micos y humanos con el fin de adelantar acciones de investigaci?n para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 1 records from Capalictus, a new subgenus of Lasioglossum Curtis, 1833 from South Africa, with description of three new species (Hymenoptera, Apoidea, Halictidae). 1 records from A synopsis of the genus Dorcasta Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Apomecynini). 175 records from Nannofossil abundance of Hole 41-366A. 100 records from Anfibios y reptiles de la desembocadura del ca?o Teracay en el r?o Tomo, Puerto Carre?o, Vichada - Proyecto Colombia Bio. 16069 records from Inventaire des Mammif?res marins de France (m?tropole et outre-mer). 2 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 1 records from A new species and key to all known species of Confusacris Yin & Li, 1987 (Orthoptera: Acrididae) from China. 64 records from Lynx 1996 pr?sence Occasionnelle Mailles 10km R?seau Loup-Lynx ONCFS. 136 records from Nannofossil abundance of Hole 39-359. 31 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 1119 records from Outer Hebrides Insect Records from Literature. 4159 records from DBG Mirabilis rotundifolia Demographic Monitoring. 6 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 3 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 211 records from Stadt K?nigs Wusterhausen. 217 records from Inventaire des odonates 2014. 152 records from Nannofossil abundance of Hole 49-412. 26 records from Abundance of benthos infauna at station PS1240-1. 1957 records from BioGIS - Marine snails - HUJ collections. 111 records from ?kologischer Weinberg (Guntersblum). 611 records from Donn?es du R?le gris sur le territoire de la Guadeloupe. 8 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 5 records from Review of the Nassarius pauperus (Gould, 1850) complex (Nassariidae): Part 3, reinstatement of the genus Reticunassa, with the description of six new species. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 2203 records from Molluscus specimens of Toyohashi Museum of Natural History. 33 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 50902 records from Anfibios y reptiles de las regiones 30 (Parque Natural Sierra Maderas del Carmen); 31 (Sierra El Burro-R?o San Rodrigo); 36 (Sierra La Encantada); y 37 (Sierra El Pino), Coahuila. 688 records from donn?es arachnologiques de CARR David. 19 records from Fishes from the Auckland and Campbell Islands, Cape Expedition, 1942-1944. 40 records from Two new species of Ecpatia Turner, 1902, and the first records of Ecpatia sciachroa Hampson, 1926 and Ecpatia obscura Holloway, 2009 from Thailand (Lepidoptera: Noctuidae, Noctuinae). 48 records from Ruhrwiesen bei Neheim-H?sten. 293 records from Macrofauna, entomofauna y vegetaci?n vascular de la Isla Cayo Serranilla durante la Expedici?n Seaflower 2017 - Proyecto Colombia BIO. 22 records from Nannofossil abundance of Hole 3-22. 2 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 120 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-14. 271 records from ABC Matandwe Forest Reserve Vegetation Survey. 50049 records from Fungi of Costa Rica (INBio). 68177 records from Intermountain Herbarium (Utah State University). 1350 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 48 records from Planktic foraminifera abundance of Hole 25-241. 1873 records from Microbial community structure of chronically polluted marine sediments from a cold region of the southern hemisphere. 91352 records from ?????????????????? Resources survey and education advocacy to promote for Taiwan amphibian resources. 1576 records from (Appendix B) Nannofossil abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 134 records from BIRDRACE Griffin Wood Warblers. 184 records from Kystfuruskoger 2015. 156 records from Deep-Sea holothurians (Echinodermata, Holothuroidea) of the Colombian Southern Caribbean Sea. 1 records from On a new marine podocopid genus and species (Ostracoda: Hemicytheridae) from Brazil. 1 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 2 records from Microzooplankton abundance and biomass at station TT054_24-22. 3 records from A new species of freshwater crab of the genus Himalayapotamon Pretzmann, 1966 (Decapoda, Brachyura: Potamidae: Potaminae) from Uttarakhand, northern India. 1 records from Synonymies, a new combination, and four new species in Amphicnaeia Bates (Coleoptera: Cerambycidae: Lamiinae). 4345 records from Gunma Museum of Natural History, Fungi Specimen. 3070 records from Colecci?n Cient?fica de Referencia Zool?gica del Choc?- Herpetolog?a. 58 records from Comunidad ?ctica de la Isla Cayo Serranilla durante la Expedici?n Seaflower 2017 - Proyecto Colombia BIO. 2 records from HZI (GBF) Reichenbach Collection of Myxobacteria. 5 records from Regenwasserabfangbecken Erlenbach. 33182 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 369 records from Donn?es du/de la naturaliste BLAQUIERE Anne provenant de la base de donn?e du SINP ?le-de-France CETTIA. 12558 records from Bacterial diversity in snow from mid-latitude mountain areas: Alps, Eastern Anatolia, Karakoram and Himalaya.. 425 records from Percentages of planktonic foraminifera species in sediment core V22-38. 12 records from Nano and microzooplankton abundance and biomass at station NBP97-01-04-1. 35 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 4 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 5 records from Three new species of spinicaudatan clam shrimps from Australia, all from gnammas (rock pools). 180 records from (Table 6) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides in DSDP Hole 79-545. 157 records from Abundance of radiolaria at station UT99-21-2. 40 records from Donn?es naturalistes de Fabrice CRABOS. 1 records from A new brachypterous Filchneria and two new generic records for China, Arcynopteryx and Pictetiella (Plecoptera: Perlodidae). 53 records from Birds (GNHM-BI). 1190 records from Malawi-Noctuidae-Biodiversity. 1184 records from (Table 3C) Distribution of Mesozoic nannoliths at DSDP Hole 43-384. 858 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 11 records from A review oI the Sphex flavipennis species group (Hymenoptera, Sphecidae) in northwest AIrica with description oI two new species and a discussion oI a species Irom Sardinia. 2 records from Three new species of Entomobryoidea (Collembola: Entomobryomorpha) from Brazilian Caatinga-Cerrado transition, with identification keys to Brazilian Cyphoderus, Pseudosinella and Trogolaphysa species. 1658 records from ZUEC-HEM - Cole??o de Hemiptera do Museu de Zoologia da UNICA
Keywords: GBIF; biodiversity; species occurrences